Functional sustained release composition and molded product thereof
By using pore volume combined with matrix resin with a specific acid dissociation constant and metal ion radius in the functional sustained release solution, the problem of maintaining the functional sustained release effect for a long time in the prior art is solved, and efficient functional sustained release and shape maintenance are achieved.
Patent Information
- Application Number
- JP2025011896
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-01-28
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art is difficult to achieve long-term maintenance of functional sustained release effects, especially in maintaining shape and increasing the content of functional components.
By using pore volumes with a specific acid dissociation constant and metal ion radius range in the functional sustained release liquid, combined with a matrix resin, a functional sustained release composition with high affinity is formed.
The functional sustained release composition maintains excellent sustained release effect over the long term, improves the performance and service life of the product, while reducing maintenance frequency and cost.
Smart Images

Figure 2025066142000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a functional sustained-release composition and a molded article thereof. [Background technology]
[0002] In functional ingredients such as small animal control, antibacterial, antiviral, and sliding oil, a specified amount of functional By releasing the ingredients for a long period of time, it is expected that the effect will last longer. As a way to increase the duration of the effect of the compound, the small animal control functional ingredient was applied to the matrix resin. Molded bodies using composite materials for controlling small animals have been proposed (for example, Patent Documents 1 to 3). The molded articles described in Patent Documents 1 to 3 gradually release small animal control functional ingredients onto the surface of the molded article. (hereinafter referred to as "slow release"), the surface of the molded article that comes into contact with small animals such as pests In order to maintain this sustained release effect for a long period of time, One possible solution is to increase the amount of functional components added to the tethered resin. Increasing the amount of functional ingredients is also effective from the viewpoint of further enhancing their functions. In order to increase the affinity between the functional component and the matrix resin, functional groups are added to the functional component. By modifying the matrix resin, increasing the polarity of the matrix resin, or supporting functional components on the porous material, Furthermore, there is a method for forming a porous body having a large specific surface area (for example, Patent Document 4). A functional sustained-release composition using a porous coordination polymer as a porous body has also been devised (Patent Document 5). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2001-73886 A [Patent Document 2] JP 2000-212005 A [Patent Document 3] JP 2008-206492 A [Patent Document 4] JP 2012-6868 A [Patent Document 5] JP 2019-218310 A Summary of the Invention [Problem to be solved by the invention]
[0004] In order to apply liquid functional ingredients to the matrix resin, Functional ingredients can be placed in the free volume space, or the resin can be spread apart and functional ingredients can be placed in the gaps between the resins. In this case, it is possible to arrange the functional component and the matrix resin. The higher the affinity, the easier it is to arrange the functional component, and the greater the amount of the functional component can be placed on the matrix. It can be developed into a resin.
[0005] However, in order to maintain the shape of the molded product, a skeleton is formed by the matrix resin. Therefore, the free volume in the matrix resin is determined by the type of resin and thermal vibration due to temperature. In addition, even if you try to expand the space between the resins by using functional ingredients, In order to maintain the shape of the molded product, the distance between the resins must be less than a certain distance. There is also an upper limit to the volume, and there is a limit to increasing the amount of functional components. In the case of plastic resins, the polarity of the matrix resin is usually adjusted to modify the resin. However, the content of the functional component in the entire molded product is limited to about 20% by mass. While doing so, we will select the matrix according to the performance and price required when using it, such as the durable temperature, strength, and material unit price. Therefore, the selection of functional sustained release resins that can maintain the sustained release effect for a long period of time is limited. It is difficult to realize a suitable composition and a molded article thereof.
[0006] On the other hand, the functional component is not limited to the matrix resin, but may be adsorbed and supported on a porous material. It can be added to the resin by melt kneading. The porous media are usually porous coordination polymers, zeolites, silica, alumina, molecular Possible examples of such porous materials include activated carbon and activated charcoal. These porous materials support and adsorb functional components. In addition to the adsorption area of the pores, affinity with the adsorption surface is also important. In addition to the amount of the drug adsorbed on the matrix, it also has a large effect on the rate of release from the matrix resin. There are various functional ingredients, and the porous bodies that have high affinity with the functional ingredients are Therefore, we have developed a formula that takes into account the compatibility with functional ingredients. Designing the materials used in a shape is extremely difficult.
[0007] Therefore, an object of the present invention is to provide a functional sustained-release composition capable of maintaining an excellent sustained-release effect for a long period of time. The present invention also provides a composition and a molded article thereof. [Means for solving the problem]
[0008] As a result of intensive research to solve the above problems, the present inventors have discovered that the acid dissociation of functional sustained-release liquid When the metal ion radius of the porous body is within a specific range with respect to the constant, the obtained function of sustained release The present invention has been completed based on the discovery that a polymeric composition can solve the above problems.
[0009] That is, the present invention is as follows. ( 1 ) A porous body having a functional sustained-release liquid and metal ions is provided, and the acid dissociation constant α of the functional sustained-release liquid is wherein the radius R of the metal ion satisfies the range of the following formula 1: A composition and a molded article thereof. JPEG2025066142000002.jpg22129 ( 2 ) The metal ion is at least one of an alkali metal, an alkaline earth metal, and a transition metal. A sustained-release composition and a molded product thereof having the function (1). ( 3 ) The radius R of the metal ion is 40×10 -12 m to 150×10 -12 m is in the range ( 1 ) or (2) A functional sustained-release composition and a molded body thereof. ( 4 ) The acid dissociation constant α of the functional sustained-release liquid is within the range of -10 to 40 (1) to (3). The functional sustained release composition and its molded article. ( 5 ) The porous material is a porous coordination polymer consisting of metal ions and organic ligands (1). The functional sustained-release composition and its molded body according to any one of claims 1 to 4. Effect of the Invention
[0010] According to the present invention, a functional sustained-release composition and a molded product capable of maintaining an excellent sustained-release effect for a long period of time are provided. The body can be donated. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Example 1, where the functional sustained-release liquid is etofenprox. [Diagram 2]FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Example 2, where the functional sustained-release liquid is etofenprox. [Diagram 3] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Example 3, where the functional sustained-release liquid is etofenprox. [Figure 4] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Example 4, where the functional sustained-release liquid is etofenprox. [Diagram 5] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Example 5, where the functional sustained-release liquid is etofenprox. [Figure 6] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Example 6, where the functional sustained-release liquid is etofenprox. [Figure 7] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Example 7, where the functional sustained-release liquid is etofenprox. [Figure 8] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Example 8, where the functional sustained-release liquid is etofenprox. [Figure 9] FIG. 1 shows the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Comparative Example 1-1, where the functional sustained-release liquid is etofenprox. [Figure 10] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Comparative Example 1-2, where the functional sustained-release liquid is etofenprox. [Figure 11] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Comparative Example 1-3, where the functional sustained-release liquid is etofenprox. [Figure 12] FIG. 13 is a diagram showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 9, where the function-release liquid is 2-n-octyl-4-isothiazolin-3-one. [Figure 13] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 10, where the function-release liquid is 2-n-octyl-4-isothiazolin-3-one. [Figure 14] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 11, where the function-release liquid is 2-n-octyl-4-isothiazolin-3-one. [Figure 15] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 12, where the function-release liquid is 2-n-octyl-4-isothiazolin-3-one. [Figure 16] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 13, where the function-release liquid is 2-n-octyl-4-isothiazolin-3-one. [Figure 17] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 14, where the function-release liquid is 2-n-octyl-4-isothiazolin-3-one. [Figure 18] FIG. 13 is a diagram showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 2-1, where the function-release liquid is 2-n-octyl-4-isothiazolin-3-one. [Figure 19] FIG. 13 is a diagram showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 2-2, where the function-release liquid is 2-n-octyl-4-isothiazolin-3-one. [Figure 20]FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 2-3, where the function-release liquid is 2-n-octyl-4-isothiazolin-3-one. [Figure 21] FIG. 13 is a diagram showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 2-4, where the function-release liquid is 2-n-octyl-4-isothiazolin-3-one. [Figure 22] FIG. 13 is a diagram showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 2-5, where the function-release liquid is 2-n-octyl-4-isothiazolin-3-one. [Diagram 23] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 15, where the function-release liquid is methyl anthranilate. [Figure 24] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 16, where the function-release liquid is methyl anthranilate. [Diagram 25] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 17, where the function-release liquid is methyl anthranilate. [Figure 26] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 18, where the function-release liquid is methyl anthranilate. [Figure 27] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 19, where the function-release liquid is methyl anthranilate. [Figure 28] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 20, where the function-release liquid is methyl anthranilate. [Figure 29]FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 3-1, where the function-release liquid is methyl anthranilate. [Diagram 30] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 3-2, where the function-release liquid is methyl anthranilate. [Diagram 31] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 3-3, where the function-release liquid is methyl anthranilate. [Diagram 32] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 3-4, where the function-release liquid is methyl anthranilate. [Diagram 33] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 3-5, where the function-release liquid is methyl anthranilate. [Diagram 34] FIG. 2 shows the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 21, where the function-release liquid is 5-heptyloxolan-2-one. [Diagram 35] FIG. 2 shows the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 22, where the function-release liquid is 5-heptyloxolan-2-one. [Diagram 36] FIG. 2 shows the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 23, where the function-release liquid is 5-heptyloxolan-2-one. [Figure 37] FIG. 2 shows the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 24, where the function-release liquid is 5-heptyloxolan-2-one. [Figure 38]FIG. 2 shows the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Example 25, where the functional sustained-release liquid is 5-heptyloxolan-2-one. [Figure 39] FIG. 2 shows the relationship between the number of repeated washings and the surface amount of the functional-release liquid in the functional-release composite molded body in Example 26, where the functional-release liquid is 5-heptyloxolan-2-one. [Diagram 40] FIG. 2 shows the relationship between the number of repeated washings and the surface amount of the functional-release liquid in the functional-release composite molded body in Example 27, where the functional-release liquid is 5-heptyloxolan-2-one. [Diagram 41] FIG. 2 shows the relationship between the number of repeated washings and the surface amount of the functional-release liquid in the functional-release composite molded body in Example 28, where the functional-release liquid is 5-heptyloxolan-2-one. [Diagram 42] FIG. 2 shows the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 29, where the function-release liquid is 5-heptyloxolan-2-one. [Diagram 43] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 30, where the function-release liquid is 5-heptyloxolan-2-one. [Diagram 44] FIG. 13 is a diagram showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 4, where the function-release liquid is 5-heptyloxolan-2-one. [Diagram 45] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded product in Example 31, where the functional sustained-release liquid is chlorpyrifos. [Figure 46] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded product in Example 32, where the functional sustained-release liquid is chlorpyrifos. [Figure 47]FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Comparative Example 5-1, where the functional sustained-release liquid is chlorpyrifos. [Figure 48] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Comparative Example 5-2, where the functional sustained-release liquid is chlorpyrifos. [Figure 49] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Comparative Example 5-3, where the functional sustained-release liquid is chlorpyrifos. [Figure 50] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Comparative Example 5-4, where the functional sustained-release liquid is chlorpyrifos. [Figure 51] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Comparative Example 5-5, where the functional sustained-release liquid is chlorpyrifos. [Figure 52] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Comparative Example 5-6, where the functional sustained-release liquid is chlorpyrifos. [Diagram 53] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Comparative Examples 5-7, where the functional sustained-release liquid is chlorpyrifos. [Figure 54] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Comparative Examples 5-8, where the functional sustained-release liquid is chlorpyrifos. [Figure 55] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the functional sustained-release liquid in the functional sustained-release composite molded body in Comparative Examples 5-9, where the functional sustained-release liquid is chlorpyrifos. [Figure 56] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 33, where the function-release liquid is dimethyl sulfoxide. [Figure 57]FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 34, where the function-release liquid is dimethyl sulfoxide. [Figure 58] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 35, where the function-release liquid is dimethyl sulfoxide. [Figure 59] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 36, where the function-release liquid is dimethyl sulfoxide. [Figure 60] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Example 37, where the function-release liquid is dimethyl sulfoxide. [Figure 61] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 6-1, where the function-release liquid is dimethyl sulfoxide. [Figure 62] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 6-2, where the function-release liquid is dimethyl sulfoxide. [Figure 63] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 6-3, where the function-release liquid is dimethyl sulfoxide. [Figure 64] FIG. 13 is a graph showing the relationship between the number of repeated washings and the surface amount of the function-release liquid in the function-release composite molded body in Comparative Example 6-4, where the function-release liquid is dimethyl sulfoxide. [Figure 65] FIG. 1 is a diagram showing the relationship between the metal ion radius of the porous body and the exponential ratio of the surface amount of the function sustained-release liquid after repeated washing in Examples 1 to 8 and Comparative Examples 1-1 to 1-3, where the function sustained-release liquid is etofenprox. [Figure 66]FIG. 13 is a graph showing the relationship between the metal ion radius of the porous body and the exponential ratio of the surface amount of the function-release liquid after repeated washing in Examples 9 to 14 and Comparative Examples 2-1 to 2-5, where the function-release liquid is 2-n-octyl-4-isothiazolin-3-one. [Figure 67] FIG. 13 is a diagram showing the relationship between the metal ion radius of the porous body and the exponential ratio of the surface amount of the function-release liquid after repeated washing in Examples 15 to 20 and Comparative Examples 3-1 to 3-5, where the function-release liquid is methyl anthranilate. [Figure 68] FIG. 13 is a graph showing the relationship between the metal ion radius of the porous body and the exponential ratio of the surface amount of the function-release liquid after repeated washing in Examples 21 to 30 and Comparative Example 4, where the function-release liquid is 5-heptyloxolan-2-one. [Figure 69] FIG. 13 is a diagram showing the relationship between the metal ion radius of the porous body and the exponential ratio of the surface amount of the function sustained-release liquid after repeated washing in Examples 31 to 32 and Comparative Examples 5-1 to 5-9, where the function sustained-release liquid is chlorpyrifos. [Figure 70] FIG. 13 is a diagram showing the relationship between the metal ion radius of the porous body and the exponential ratio of the surface amount of the functional sustained-release liquid after repeated washing in Examples 33 to 37 and Comparative Examples 6-1 to 6-4, where the functional sustained-release liquid is dimethyl sulfoxide. [Figure 71] FIG. 7 is a diagram showing the relationship between the acid dissociation constant of the functional sustained-release liquid and the slope of the linear approximation equation of FIGS. [Figure 72] FIG. 7 is a diagram showing the relationship between the acid dissociation constant of the functional sustained-release liquid and the intercept of the linear approximation equation of FIGS. [Figure 73] FIG. 1 is a diagram showing the relationship between the acid dissociation constant of a functional sustained-release liquid and the metal ion radius R of a porous body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described as necessary. The present embodiment is an example for explaining the present invention. The disclosure is not limited to the embodiments described herein.
[0013] [Functional sustained release composition] The functional sustained-release composition of this embodiment is a functional sustained-release liquid and a functional sustained-release liquid having an acid dissociation constant of 1000 to 15000. The porous body is made of metal ions having a metal ion radius within a range of values. The functional sustained-release composition of this embodiment comprises a functional sustained-release liquid and a porous composite material. By combining interfacial polymers and matrix resins, excellent sustained release effects can be achieved for a long period of time. Therefore, the functional sustained release composition of this embodiment is useful for improving the performance of products and for maintenance. This has the advantage of reducing costs by reducing the frequency of authentication.
[0014] [Functional sustained release liquid] The "function-sustained release" of the functional sustained release liquid includes, for example, the function of controlling small animals and the function of promoting plant growth. Functions that control the length of the resin, antibacterial function, antifungal function, function that gives plasticity to the resin, sliding function, Self-repairing function, catalytic function, medical function, anti-virus function, self-cleaning function, etc. A functional sustained-release liquid is a liquid ingredient that has a sustained release function. The composition may be in the form of a liquid made of a solid component having a sustained release function. The composition may be in a liquefied form obtained by dissolving a solid component having such properties in a solvent.
[0015] Examples of functional liquids having a small animal control function include liquids for controlling various agricultural pests, sanitary pests, Other insecticides or solvents that have control activity against small animals such as insects, spiders, mites, and mice The agent may be in the form of a liquid dissolved in water (hereinafter also referred to as a "small animal control agent"). For example, compounds having small animal repellent activity, insecticidal activity, acaricidal activity, spidericidal activity or rodenticidal activity Compounds having antifeedant activity for small animals, and compounds having anti-feedant activity for small animals Examples of compounds having growth control activity include:
[0016] Specific examples of small animal control drugs include metadiamide insecticides such as broflanilide, Piperidine insecticides such as azin, chloronicotinyl insecticides such as imidacloprid, Compounds consisting of neophyl radicals with silicon atoms such as ruofen, benfuracarb , alanycarb, methoxydiazone, carbosphan, fenobucarb, carbaryl, meth Carbamate compounds such as somil, propoxar, and fenoxycarb, pyrethrins, and allergens Surin, dl, d-T80-Allethrin, d-T80-Resmethrin, Bioallethrin Phosphorus, d-T80-phthalthrin, phthalthrin, resmethrin, furamethrin, propane permethrin, acrinathrin, etofenprox, tralomethrin, phene Nothrin, d-fenothrin, fenvalerate, empenthrin, prallethrin, tef Pyrethroids such as fluthrin, benfluthrin, transfluthrin, and metofluthrin Compounds, dichlorovos, fenitrothion, diazinon, malathion, bromophos, fe thion, trichlorfon, naled, temephos, fenclofos, chlorpyrifos-methyl , cyafos, carclofos, azamethiphos, pyridaphenthion, propetamphos, clo Examples of the organic phosphorus compounds include rupyrifos and the like, as well as their isomers, derivatives, and analogues.
[0017] In addition, examples of compounds having growth control activity in small animals include methoprene, Pyriproxyfen, Kinoprene, Hydroprene, Deohenolan, NC-170, Fructoside Examples of such antibacterial agents include phenoxuron, diflubenzuron, lufenuron, and chlorazuron.
[0018] Examples of compounds having animalicidal activity include Kelthane, chlorfenavir, and Debuf. Acaricides such as phenpyradpyridaben, milbemectin, and fenpyroximate, and silico , norbomide, zinc phosphide, thallium sulfate, yellow phosphorus, anthraquinone, warfarin, endosa Examples of rodenticides include cyclohexyl ether, coumarin, coumatetralin, promagilolone, and difethialone. can be done.
[0019] In addition, examples of small animal control agents include Taiwan cypress, Asunaro, and Hinoki Asunaro. (Aomori Hiba) and other plants, and cypress and herbs. (α-cadinol, T-cadinol), clove, nutmeg, coriander, kumi Geraniol, pinene, caryophyllene, borneol, and other aromatic oils are found in large amounts in aromatic plants such as ginger, ginger, and ginger. Examples of agents derived from natural sources include eugenol, balm oils known to have small animal control properties, such as cedar. can be done.
[0020] In addition, as a small animal control agent, ferrocene, which has an attractant effect and a communication-inhibiting effect on insects, etc. Pheromone agents are also used. For example, the product "Confuse" by Shin-Etsu Chemical Co., Ltd. Confuser R", "Confuser AA", "Confuser N", "Confuser MM" , "Hamakikon-N", "Sukashibakon-L", "Shinkuikon-L", and "Nashihimekon" Pheromone agents used for fruit trees such as "Bokutokon-H" and "Hetamushikon", Shin-Etsu Chemical industrial products "Confuser V", "Yotokon-H", "Yotokon-S", "Co Pheromone agents used on vegetables such as "Nagakon Plus" and "Shin-Etsu Konagakon" Pheromone agents used in tea such as "Hamakikon-N" by Shin-Etsu Chemical Co., Ltd. "Okimerakon", "Yotoukon-I", "Kebukakon" and other varieties are used for sugarcane. Pheromone agents are included.
[0021] Furthermore, the small animal control agent may be a repellent for hornet bees, The repellent contains, for example, a compound represented by the following general formula (I) as an active ingredient.
[0022] [ka]
[0023] In formula (I), R1 is a hydrogen atom, a C 1 - 4 Alkyl groups, C which may have a substituent β 2 - 4 An alkenyl group or a substituent β may be included. C 1 - 4 represents an alkyl-carbonyl group, and X is a C 1 - 4 C which may have an alkylene group or a substituent γ 2 - 4 represents an alkenylene group, and α is , C optionally having a substituent δ 1 - 4 C2, which may have an alkyl group or a substituent δ - 4 Alkenyl group, optionally having a substituent δ 1 - 4 Alkoxy group, having a substituent δ C 1 - 4 Alkyl-carbonyl group, optionally having a substituent δ 1 - 4. One or more substituents selected from an alkyl-carbonyloxy group, a halogeno group, and a hydroxyl group The substituents β, γ and δ each independently represent 1 - 4 Alkoxy group, C 1 - 4 alkyl-carbonyl group, C 1 - 4 Alkyl-carbonyloxy group, halogeno group and water represents one or more substituents selected from the group consisting of an acid group, and n is an integer of 0 to 5. show.
[0024] Further specific examples of repellents for hornets include those described in JP 2017-88548 A. Examples of repellents include those described in the publication.
[0025] An example of a functional sustained-release liquid that controls plant growth is a plant hormone. Plant hormones include, for example, indole-3-acetic acid and 2,4-dichlorophenoxyacetic acid. Natural or synthetic auxins such as zeaxanthin, 2,6-dichlorobenzoic acid, and naphthalene acetic acid, Natural or synthetic amino acids such as benzylaminobenzimidazole, kinetin, 4-benzylaminobenzimidazole, and benzyladenine Synthetic cytokinins; gibberellins; brassinolide, castasterone, and other brassinolides These plant hormones include steroids and abscisic acid. Or two or more types may be used in combination.
[0026] Examples of the functional sustained-release liquid having antibacterial and antifungal functions include known sustained-release liquids. Examples of the antibacterial agent and the antifungal agent having a sustained release property include: For example, hinokitiol compounds, chitosan compounds, mustard extract compounds, eucalyptus compounds, etc. These compounds include natural organic compounds such as benzoyl peroxides, synthetic organic compounds, and organic composite agents. The substances are used singly or in combination of two or more. From the viewpoint of being effective against both mold and mildew, synthetic organic compounds are preferred.
[0027] Examples of synthetic organic compounds include nitrogen-containing heterocyclic compounds, aldehyde compounds, and fluorine compounds. Enol compounds, biguanide compounds, nitrile compounds, halogen compounds, aniline compounds Lithium compounds, disulfide compounds, thiocarbamate compounds, organosilicon quaternary amines Ammonium salt compounds, quaternary ammonium salt compounds, amino acid compounds, organometallic compounds substances, alcohol compounds, carboxylic acid compounds, ester compounds, thiazoline compounds These synthetic organic compounds may be used alone or in combination with other compounds such as cationic polymers. is used in combination of two or more types.
[0028] Examples of functional sustained-release liquids that have the function of imparting plasticity to resins include carboxylic acids. Ester derivatives, phosphate derivatives, phosphazene derivatives, carboxylic acid amide derivatives , sulfonic acid ester derivatives, and sulfonamide derivatives. These may be used alone or in combination of two or more.
[0029] Examples of the carboxylate derivatives include those having a hydroxyl group, a nitro group, an amino group, an epoxy group, Alkyl esters of various carboxylic acids, which may be substituted with groups, halogens, etc., and aromatic esters Specific examples of the carboxylate derivatives include dimethyl phthalate. phthalate, diethyl phthalate, di-n-octyl phthalate, diphenyl phthalate, benzyl phthalate, dimethoxyethyl phthalate, 4,5-epoxyhexahydrophthalate Di(2-ethylhexyl)phthalate, Di(7, 8-epoxy-2-octenyl), 4,5-epoxycyclohexahydrophthalic acid di( 9,10-epoxyoctadecyl), 4,5-epoxycyclohexahydrophthalic acid diester (10,11-epoxyundecyl), di(tetrahydrofurfuryloxyethyl) phthalate ), various mixed phthalate esters and ethylene oxide adducts of mixed phthalate esters, etc. Phthalate derivatives, isophthalate derivatives, tetrahydrophthalate Derivatives, butoxyethyl parahydroxybenzoate, cyclohexyl parahydroxybenzoate 2-Ethylhexyl parahydroxybenzoate, ω-Al Hydroxybenzoic acid ester of alkyl oligoethylene oxide, undecyl glycidyl ester Benzoic acid ester derivatives such as parahydroxybenzoic acid adduct of ter, thiodipropionic acid Propionate derivatives such as di(tetrahydrofurfuryloxyethyl), adipic acid Ester derivatives, azelaic acid ester derivatives, sebacic acid ester derivatives, dodecane 2-Acid ester derivatives, maleic ester derivatives, fumaric ester derivatives, trimet Tri(butoxyethoxyethyl) citrate, di-n-octyl citrate 1-mono (nonylphenoxyethyl), tri-n-octyl citrate, di-octyl citrate (Tetrahydrofurfuryloxyethyl), Trimyristyl citrate, Triethylcitrate citrate derivatives such as tetrahydrofuran, itaconic acid ester derivatives, tetrahydrofuran, oleic acid tetrahydrofuran Furfuryl and other oleic acid ester derivatives, ricinoleic acid ester derivatives, lactic acid (n-butyl ethyl), lactic acid (2-ethylhexyl), lactic acid (n-butoxyethoxyethyl), lactic acid (n -Octoxyethoxyethyl), lactic acid (n-decyloxyethoxyethyl), etc. Tartrate derivatives, di(octoxyethoxyethyl) tartrate, n-octyl tartrate (nonyl) tartrate derivatives such as di(octoxyethoxyethyl) tartrate, di(octoxyethoxyethyl) tartrate, etc. Dibutoxyethyl malate, Di(n-butoxyethoxyethyl) malate, Malic acid Malate derivatives such as distearyl, octadecenyl isononyl malate, benzyl and salicylic acid ester derivatives such as salicylic acid adduct of diglycidyl ether.
[0030] Examples of the phosphate derivatives include trimethyl phosphate and triethyl phosphate. phosphate, tributyl phosphate, tri-(2-ethylhexyl) phosphate, 2-ethylhexyl ethylhexyl diphenyl phosphate, tributoxyethyl phosphate, triphenyl Nyl phosphate, cresyl diphenyl phosphate, isodecyl diphenyl phosphite phosphate, tricresyl phosphate, trixylenyl phosphate, tri(chloroethene) xylenyl diphenyl phosphate, and tetrakis(2,4- di-tert-butylphenyl) 4,4'-biphenylene diphosphonate.
[0031] The phosphazene derivative may be, for example, a cyclic phosphazene represented by the following general formula (1): Compounds include:
[0032] [ka]
[0033] In the formula, m represents an integer of 3 to 25; 1 , and R 2 are the same but different and an alkyl group having 1 to 8 carbon atoms, or an alkyl group having 1 to 8 carbon atoms and / or The phosphazene derivative is a phenyl group which may be substituted with an aryl group or an allyl group. The cyclic phosphazene compound may be composed of one kind of cyclic phosphazene compound represented by the formula (I), or may be composed of a mixture of two or more kinds of cyclic phosphazene compounds represented by the formula (I). The configuration may be as follows:
[0034] The phosphazene derivative may be, for example, a linear phosphazene represented by the following general formula (2): Compounds are also included.
[0035] [ka]
[0036] In the formula, n represents an integer of 3 to 1000; 3 , and R 4 are the same but different and may be an alkyl group having 1 to 8 carbon atoms, or an alkyl group having 1 to 8 carbon atoms and / or an allyl group, and X represents a group -N=P(OR 3 ) 3, group -N=P(OR 4 )3, group -N=P(O)(OR 3 ) or the group -N=P(O)(OR 4 ), Y represents a group -P(OR 3 ) 4, group -P(OR 4 ) 4, group -P(O)(OR 3 )2 or Group -P(O)(OR 4 The phosphazene derivative is a linear phosphazene represented by the formula (2). It may be composed of one type of phazene compound or a mixture of two or more types. This is also fine.
[0037] The phosphazene derivative is a phosphazene derivative represented by the following formula (3): R in Equation (2) 1 , R 2 , R 3, R 4 The alkyl group is eliminated from the aryl group, forming a bridge between the two oxygen atoms. The compound may be a phosphazene compound.
[0038] [ka]
[0039] In the formula, r represents 0 or 1, and A represents a group -SO2-, -S-, -O-, or -C(CH3) Shows 2-.
[0040] Specific examples of the cyclic phosphazene compound represented by formula (1) include hexaphenoxy Cyclotriphosphazene, Octaphenoxycyclotetraphosphazene, Decaphenoxy Cyclopentaphosphazene, hexapropoxycyclotriphosphazene, octapropoxy Examples of the cyclopentaphosphazene include cyclopentaphosphazene and cyclopentapropoxy. can be done.
[0041] Specific examples of the linear phosphazene compound represented by formula (2) include linear dichlorophosphazene compounds. A chain phosphazene in which propoxy and / or phenoxy groups are substituted on arylphosphazene. Specific examples of the crosslinked structure represented by formula (3) include 4,4'-sulfonyl Diphenylene (bisphenol-S residue), 4,4'-oxydiphenylene group, 4,4 Examples of the aryl group include 4,4'-thiodiphenylene and 4,4'-diphenylene.
[0042] These phosphazene derivatives have amino and / or phenylamino groups at any position. These phosphazene derivatives may be used alone or in combination. The above may be used in combination.
[0043] Examples of the carboxylic acid amide derivatives include N-cyclohexylbenzoic acid amide. In addition, the sulfonamide derivatives include N-methyl-benzenesulfonamide. , N-ethyl-benzenesulfonamide, N-butyl-benzenesulfonamide, N- Cyclohexyl-benzenesulfonamide, N-ethyl-p-toluenesulfonamide, N N-butyl-toluenesulfonamide, and N-cyclohexyl-toluenesulfonamide. Can be obtained.
[0044] Examples of sulfonate derivatives include ethyl benzenesulfonate. Examples of sulfonic acid amide derivatives include 2-methoxyethyl methanesulfonate, 2,2,2-Trifluoroethyl ethanesulfonate, Methyl p-toluenesulfonate, p- Examples thereof include ethyl toluenesulfonate and n-propyl p-toluenesulfonate.
[0045] Examples of the functional sustained-release liquid having a sliding function include known sliding agents having sustained release properties. Examples of known sliding agents include mineral oil, synthetic oil, wax, and paraffin. Can be obtained.
[0046] Examples of the self-repairing functional sustained-release liquid include known self-repairing functional sustained-release liquids. Known self-repairing agents include polyrotaxane, self-healing clear (naphthalene), etc. (Products of Toko Shoji Co., Ltd.)
[0047] Examples of the functional sustained-release liquid having a catalytic function include known catalysts having sustained-release properties. Known catalysts include ionic liquids, tertiary amines (e.g., Tosoh Corporation products), "PZETA", etc.), organotitanium compounds (e.g., tetra-i-propoxytitanium , tetra-n-butoxytitanium, tetrakis(2-ethylhexyloxine) titanium (For example, products from Nippon Soda Co., Ltd.)
[0048] Examples of functional sustained-release liquids having medical functions include known medical products having sustained-release properties. Can be obtained.
[0049] The functional sustained-release liquid having antiviral function is, for example, an aromatic compound (Amorden V- 1000HP, Yamato Chemical Industry Co., Ltd.), cationic polymer system (Amorden D-CL50, D- CLH, manufactured by Yamato Chemical Industry Co., Ltd.
[0050] Examples of functional sustained-release liquids having a self-cleaning function include ionic surfactants. (Aminoion AS200, AS400, Nippon Nyukazai Co., Ltd.), non-ionic surfactants (Amit 102, 1 05, Kao), fluorosurfactants (Surflon S-242, S-243, S-386, AGC Sei Chemical (manufactured by)
[0051] The solvent has high compatibility with the matrix resin and has little effect on the shape stability of the molded product. A small solvent is preferable. Examples of the solvent include water, methanol, ethanol, and dimethyl. sulfoxides, polyethylene glycols, sulfonamide derivatives, sulfonate esters derivatives, carboxylic acid amide derivatives, carboxylic acid ester derivatives, phosphate ester derivatives, Examples of the compounds include hydrocarbon-based compounds and silicone-based compounds.
[0052] Sulfonamide derivatives include, for example, N-methyl-benzenesulfonamide, N- Ethyl-benzenesulfonamide, N-butyl-benzenesulfonamide, N-cyclohexane N-ethyl-p-toluenesulfonamide, N-butyl-p-toluenesulfonamide Examples of cyclohexyl-toluenesulfonamide include N-cyclohexyl-toluenesulfonamide. Examples of sulfonate derivatives include 2-methoxymethanesulfonate. Ethyl, 2,2,2-trifluoroethyl methanesulfonate, methyl p-toluenesulfonate ethyl, ethyl p-toluenesulfonate, n-propyl p-toluenesulfonate, etc. can be.
[0053] An example of the carboxylic acid amide derivative is N-cyclohexylbenzoic acid amide. can be done.
[0054] Examples of the carboxylate derivatives include dimethyl phthalate and diethyl phthalate. Di-n-octyl phthalate, diphenyl phthalate, benzyl phthalate, dimeth Di(2-ethylhexyl) 4,5-epoxyhexahydrophthalate ), 4,5-epoxycyclohexahydrophthalic acid di(7,8-epoxy-2-octeniyl) 4,5-Epoxycyclohexahydrophthalic acid di(9,10-epoxyoctadecyl) 4,5-Epoxycyclohexahydrophthalic acid di(10,11-epoxyundecyl) Sil), di(tetrahydrofurfuryloxyethyl) phthalate, various mixed phthalate esters and phthalate derivatives such as ethylene oxide adducts of mixed phthalate esters, isophthalic acid esters, Phthalate derivatives, tetrahydrophthalate derivatives, parahydroxybenzoin Butoxyethyl acetate, Cyclohexyloxyethoxyethoxyethyl parahydroxybenzoate , 2-ethylhexyl parahydroxybenzoate, ω-alkyl oligoethylene oxide Hydroxybenzoic acid ester, parahydroxybenzoic acid of undecyl glycidyl ether Benzoic acid ester derivatives such as adducts, di(tetrahydrofurfuryloxy)thiodipropionate propionic acid ester derivatives such as diethyl, adipic acid ester derivatives, azelaic acid Ester derivatives, sebacic acid ester derivatives, dodecanoic acid ester derivatives, maleic acid ester derivatives Phosphate derivatives, fumarate derivatives, trimellitate derivatives, citric acid Tri(butoxyethoxyethyl), di-n-octyl-mono(nonylphenoxy) tri-n-octyl citrate, dioctyl citrate (tetrahydrofurfuryloxy) Ethyl), trimyristyl citrate, triethyl citrate and other citrate ester derivatives , itaconic acid ester derivatives, oleic acid esters such as tetrahydrofurfuryl oleate Lactic acid (n-butyl), lactic acid (2-ethylhexyl) Lactic acid (n-butoxyethoxyethyl), Lactic acid (n-octoxyethoxyethyl) lactic acid ester derivatives such as n-decyloxyethoxyethyl lactic acid, di(octyl) tartrate (Nonylphenoxyethyl), (n-octyl) tartrate, (di- (Octoxyethoxyethyl) and other tartrate derivatives, dibutoxyethyl malate, Di(n-butoxyethoxyethyl)malate, Distearylmalate, Octadecamalate malic acid ester derivatives such as phenylisononyl, salicyl Salicylic acid ester derivatives such as acid adducts are included.
[0055] Examples of the phosphate derivatives include trimethyl phosphate and triethyl phosphate. phosphate, tributyl phosphate, tri-(2-ethylhexyl) phosphate, 2-ethylhexyl ethylhexyl diphenyl phosphate, tributoxyethyl phosphate, triphenyl Nyl phosphate, cresyl diphenyl phosphate, isodecyl diphenyl phosphite phosphate, tricresyl phosphate, trixylenyl phosphate, tri(chloro) ethyl) phosphate, xylenyl diphenyl phosphate, tetrakis(2,4- di-tert-butylphenyl) 4,4'-biphenylene diphosphonate.
[0056] Examples of the hydrocarbon compounds include linear saturated hydrocarbon compounds (paraffins), linear saturated hydrocarbon compounds (paraffins), Unsaturated hydrocarbon compounds (olefins), alicyclic hydrocarbon compounds (cycloalkanes, cycloalkenes, cycloalkynes, etc.) and aromatic hydrocarbon compounds. Among the hydrocarbon compounds, those with a molecular weight of 330 to 530 and a kinematic viscosity of 10 to 120 cSt Paraffin oil having a molecular weight of 330 to 530 is particularly preferred. is preferable from the viewpoint of easily entering the body of a small animal through the body orifices of the small animal. Hydrocarbon compounds with a molecular weight of 10 to 120 cSt are preferred because they are easily attached to the body surface of small animals. Furthermore, the use of paraffin oil is preferable because it is inexpensive and easily available. Examples of silicone compounds include dimethyl silicone and methylphenyl silicone. Polyether modified silicone, long chain alkyl modified silicone, and higher fatty acid ester Modified silicones are also usable.
[0057] Examples of flame retardants include halogen-free flame retardants such as trimethyl phosphate and triethyl phosphate. Triethyl phosphate, triphenyl phosphate, tricresyl phosphate, trixyl Cresyl diphenyl phosphate, Cresyl di-2,6-xylenyl phosphite phosphates, aromatic condensed phosphate esters, aliphatic phosphate amidates, 9,10-dihydro-9-oxa -10-Phosphaphenanthrene -10-Oxide, Melamine Cyanurate, Adekastab FP-600 ADEKA, Adeka STAB PFR ADEKA, Adeka STAB FP-900L ADEKA, Haloge The phosphate-based flame retardants include tris(chloropropyl)phosphate and tris(tribromoneopentyl)phosphate. pentyl) phosphate, halogen-containing condensed phosphate ester, tribromoneopentyl alco dibromoneopentyl glycol, tribromophenol, pentabromobenzyl Polyacrylate, Decabromodiphenyloxide, Tetrabromobisphenol- A, brominated epoxy, etc.
[0058] Since the functional sustained-release liquid must be liquid, the acid dissociation constant must be between -10 and 4. 0, and from the viewpoint of the constraints on the processing temperature of the matrix resin, It preferably has a molecular weight of 600 or less and a melting point of 10° C. or more.
[0059] The acid dissociation constant of the functional sustained-release liquid is given by the general formula of the acid being HA and the solvent being Hsol. The disequilibrium reaction is as follows: JPEG2025066142000007.jpg33147In this case, the acid dissociation constant Ka can be expressed as follows, including the solvent concentration [Hsol] in the constant: do. JPEG2025066142000008.jpg27133http: / / www.fm.ehcc.kyoto-u.ac.jp / pKa_compilation_Williams_RipinEvans.pdf The acid dissociation constant of the functional sustained release liquid was calculated based on the above literature and the neutralization titration, absorption spectrophotometer method, and capillary This was experimentally determined by Lee electrophoresis.
[0060] (Porous body) Porous bodies capable of supporting functional components include structures made of metal ions, such as Examples include porous coordination polymers, zeolites, silica, alumina, and molecular sieves. The radius of the metal ion in the porous body is determined by the acid dissociation constant of the functional sustained-release liquid. By being within the range, an excellent sustained release effect can be maintained for a long period of time. Among these, porous coordination polymers have a large support adsorption area and high design freedom for metal ions. It has the advantage of being able to cover a wide range of sustained-release liquids. A detailed explanation is provided.
[0061] (Porous coordination polymer) Porous coordination polymers are porous materials that contain metal ions and organic ligands. Coordination polymers have, for example, a structure in which metal ions are adsorbed to organic ligands. The molecules are, for example, organic ligands that can bind metal ions. Porous coordination polymers are called MOFs. (Metal-Organic Framework) or PCP (Porous Co It is also called the Ordination Polymer.
[0062] The porous coordination polymer has, for example, a large number of pores in the macropore or mesopore region, and the pore diameter ( The pore size (pore diameter) is determined by the crystal structure, so the pores have a uniform size.
[0063] Porous coordination polymers can be made by controlling the affinity of the organic ligands through their length and chemical structure. In this way, the retention of the functional liquid component can be increased and the functional liquid component can be packed in a finely packed manner. From this viewpoint, the average pore size of the porous coordination polymer is preferably equal to or larger than the molecular size of the functional sustained-release liquid. Preferably, the specific surface area of the porous coordination polymer measured by the BET method is 900 m 2 / g or more (for example , 900m 2 / g or more 10400m 2 / g or less) at 1000m 2 / g or more and 1200m is preferable. 2 / g or more is more preferable, and 2 / g or more It is particularly preferable that the specific surface area by the BET method is 900 m 2 / g or more This is in comparison with the case where a functional liquid component is directly kneaded into a matrix resin to form a composite molded body. Therefore, the porous coordination polymer can effectively develop functional liquids into the matrix resin. The average pore size of the porous coordination polymer can be determined by the BET method. The molecular diameter of the release liquid was calculated using the open source "Mol-view" by the following procedure. First, the molecule is drawn and the long and short diameters of the molecule are measured in the software. The long axis is the intermolecular distance at the longest part when the molecule is stretched linearly, and the short axis is the intermolecular distance at the longest part when the molecule is stretched linearly. Here, the "molecular diameter" corresponds to the short diameter.
[0064] The average pore size of the porous coordination polymer is determined so that the functional sustained-release liquid can be effectively developed by the matrix resin. From the viewpoint of being able to open the capsule and further improving the long-term sustained release, the diameter is preferably 0.1 to 5.0 nm. It is preferable that the thickness is 0.5 to 3.0 nm.
[0065] (Metal ions) Examples of metal ions include silver ions, aluminum ions, beryllium ions, calcium ions, and the like. Calcium ion, cadmium ion, cerium ion, cobalt ion, chromium ion, Copper ion, dysprosium ion, erbium ion, europium ion, iron ion, Gallium ion, gadolinium ion, holmium ion, indium ion, lithium ion, magnesium ion, manganese ion, molybdenum ion, neodymium ion, Nickel ion, scandium ion, samarium ion, strontium ion, terbium ion tungsten ion, thulium ion, vanadium ion, tungsten ion, yttrium ion ions, ytterbium ions, zinc ions, and zirconium ions. These metal ions may be used alone or in combination of two or more. The metal ions may be present in the porous coordination polymer in the form of a compound such as a salt.
[0066] In this embodiment, the metal ion radius of the porous coordination polymer is The formula can be found in the Lam Chemistry Collection, Shannon et al., Acta A 32 (1976) 751. .
[0067] (organic ligand) The organic ligand is preferably a bridging ligand capable of bridging to a metal ion. Examples of the terephthalic acid include 2-methylimidazole, terephthalic acid, and 2,5-dihydroxyterephthalic acid. Phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,3,5-benzenetricarboxylic acid, 4 ,4′-biphenyldicarboxylic acid, 4,4″-p-terphenyldicarboxylic acid, isophthalic acid 1,3,5-Benzenetricarboxylic acid, 1,3,5-tri-4-carboxyl Phenylbenzene, methylimidazole, 4,4′-biphenyldicarboxylic acid, fumaric acid Acid, naphthalenedicarboxylic acid, hexaazatriphenylene, 2,5-dihydroxybenzoin Acid, trimesic acid, 5-cyano-benzenedicarboxylic acid, 5-ethyl-1,3-benzodi Carboxylic acid, terephenyl-3,3′,5,5′-tetracarboxylic acid, 9,10-anthracene Helical dicarboxylic acid, imidazole, 2,2′-diamino-4,4′-stilbene dicarboxylic acid 2,2'-dinitro-stilbenedicarboxylic acid, 2,5-dihydroxyterephthalic acid acid, 3,3',5,5'-tetracarboxydiphenylmethane, 1,2,4,5-tetracarboxydiphenylmethane Rakis(4-carboxyphenyl)benzene, 4,4′,4″-s-triazine-2,4 ,6-Trail-tribenzoic acid, 2-hydroxyterephthalic acid, biphenyl-3,3′,5, 5′-Tetracarboxylic acid, biphenyl-3,4,5-tricarboxylic acid, 5-bromoisopropyl Examples include taric acid and malonic acid.
[0068] In a method for producing a functional sustained-release composition, the surface and / or the fine particles of a porous coordination polymer are After removing any residual substances that may be attached or present in the pores, the porous coordination polymer is machined. It is desirable to retain the active, sustained-release liquid. The presence of residual material may cause the porous coordination polymer and When combining functional liquids with nanoparticles, residual substances can narrow or completely block the pores. This may make it difficult to inject the functional liquid into the pores of the porous coordination polymer. As these are mixed into the functional liquid as impurities, the physical properties of the functional sustained-release liquid change and the desired effect is lost. There is a risk that results will not be obtained.
[0069] The residual substances can be removed, for example, by washing the porous coordination polymer with a solvent. Examples of the solvent used for washing include water, methanol, THF, and D MF is preferably used as the solvent, and the solvent is preferably water and / or methanol. In the case of the solvent, the molecular diameter of the solvent is small, and therefore the solvent is easily absorbed into the fine particles of the porous coordination polymer. It easily penetrates into the pores, and the residual substances in the pores can be easily removed. In the step of removing the porous coordination polymer, the porous coordination polymer may be immersed in the solvent for a long period of time. Preferably, the reaction time is 1 hour or more, and more preferably, 24 hours or more. One method for removing impurities is to remove residual substances by heat treatment. If the unreacted material or impurities are organic and you want to remove the organic matter, It is preferable to perform the heat treatment in an atmosphere in which the unreacted substances or impurities are volatile substances, If you want to remove volatile substances, it is preferable to perform vacuum heating treatment. The heating temperature is 100 After cleaning with a solvent, a heat treatment is performed to remove the solvent. A method for completely removing
[0070] (Matrix resin) The matrix resin includes one or more types of resin. Examples of the resin include thermal Thermoplastic resins include polyethylene resins, Polypropylene resin, polyvinyl chloride resin, polyvinylidene chloride resin, polyvinyl acetate resin Fat, polystyrene resin, AS resin, ABS resin, methacrylic resin, polyvinyl alcohol Resin, EVA resin, polyamide resin, polyacetal resin, polycarbonate resin, poly Phenylene ether resin, polyethylene terephthalate resin, polybutylene terephthalate resin, fluororesin, polyphenylene sulfide resin, polysulfone resin, polyaryl resin, polyetherimide resin, polyethersulfone resin, polyetherketone resin Liquid crystal polyester resin, thermoplastic polyimide resin, and thermoplastic polyurethane resin Examples of thermosetting resins include epoxy resins, unsaturated polyester resins, and phenolic resins. resin, urea resin, melamine resin, alkyd resin, silicone resin, polyimide resin, Polyurethane resin, vinyl ester resin, diallyl phthalate resin, furan resin, polya Minobismaleimide resin, casein resin, epoxy acrylate resin, urethane acrylate resin, polyurea resin, benzoxazine resin, oxetane resin, xylene resin, Cyclopentadiene resins, and episulfide resins.
[0071] The ratio of the content of the functional sustained-release liquid to the content of the porous coordination polymer is, for example, 1.0 From the viewpoint of more effectively and reliably achieving the effects of the present invention, the range is 1.5 to 3. It is preferably 0.
[0072] The content of the matrix resin in the functional sustained release composition is, for example, about 10 to 95% by mass. may be also possible.
[0073] (Inorganic filler) The functional sustained-release composition may contain an inorganic filler from the viewpoint of improving mechanical properties. As the inorganic filler, a known inorganic filler is used, for example, a particulate inorganic filler, a fibrous inorganic filler, or the like. Examples of particulate inorganic fillers include inorganic fillers and scaly or plate-like inorganic fillers. For example, even if the particulate inorganic filler has a micron size, the particulate inorganic filler may have a nano size. Examples of particulate inorganic fillers having a micron size include For example, calcium carbonate particles, silica particles, glass beads, titanium oxide particles, zinc oxide particles, Potassium titanate particles, titania particles, monoclinic titania particles, calcium phosphate particles, Examples of the material include wollastonite, vermiculite, shirasu balloons, and glass balloons. Examples of particulate inorganic fillers having nano-size include nano titanium oxide, nano silica, Examples of inorganic fillers include carbon black and carbon filler. is used in combination of two or more types.
[0074] Among these, particulate inorganic fillers are effective in providing sustained release of functional liquids (especially small animal control agents). From the viewpoint of being more excellent in terms of the above, potassium titanate particles are preferable. From the viewpoint of not adversely affecting the appearance of the molded article, the average fiber diameter is 0.05 to 10 μm, and It is preferable that the filler is a fibrous inorganic filler having an average fiber length of 3 to 150 μm. A fibrous inorganic filler having an average fiber diameter of 100 to 7 μm and an average fiber length of 5 to 50 μm. It is more preferable to do so.
[0075] The fibrous inorganic filler may be, for example, a fibrous inorganic filler having a micron size. The filler may be a fibrous inorganic filler having a nano size. Examples of the fibrous inorganic filler include glass fiber, carbon fiber, graphite fiber, and aramid fiber. , vinylon fiber, polyamide fiber, polyester fiber, cotton, hemp fiber, kenaf fiber, bamboo fiber Fiber, rayon, steel fiber, aluminum fiber, gypsum fiber, potassium titanate fiber, 6 Potassium titanate fiber, 8 Potassium titanate fiber, Titania fiber, Monoclinic titania fiber Examples of nano-sized fibers include silica fibers, wollastonite, and xonotlite. Examples of fibrous inorganic fillers include carbon fibers, carbon nanotubes, and fullerenes. Len, cotton fibril, silicon nitride whisker, alumina whisker, silicon carbide whisker These fibrous inorganic fillers can be used alone. or a combination of two or more types.
[0076] Examples of the scale-like or plate-like inorganic filler include scale-like or plate-like inorganic fillers having a micron size. The filler may be an inorganic filler, or a scale-like or plate-like inorganic filler having a nano-size. Examples of the scale-like or plate-like inorganic filler having a micron size include talc and kaolin. Clay, mica (synthetic or natural), glass flakes, aragonite, calcium sulfate Calcium, Aluminum Hydroxide, Potassium Titanate, Potassium Lithium Titanate, Titanium Examples of nanoparticles include potassium magnesium oxide, sericite, plate-like alumina, and boron nitride. Examples of sized scaly or plate-like inorganic fillers include organic montmorillonite, Examples of swellable synthetic mica, graphite, etc. are scaly inorganic fillers. They may be used alone or in combination of two or more. The inorganic filler may be used as it is, From the viewpoint of improving the interfacial adhesion with resin and further improving the mechanical properties, Silane coupling agents such as polysilane, epoxy silane, acrylic silane, etc. or titanate The surface of the resin may be treated with a surface treatment agent such as a coupling agent.
[0077] (Weather resistance additive) The functional sustained-release composition is provided with a weather resistance imparting agent from the viewpoint of further improving the weather resistance when left outdoors. Additives may be included. Examples of weather resistance additives include hindered phenol-based antioxidants. agents, phosphorus-based antioxidants, ultraviolet absorbing light stabilizers, hindered amine light stabilizers, and carbon blacks. One selected from the group consisting of bon.
[0078] Examples of the hindered phenol-based antioxidant include pentaerythritol tetrakis(II) and tetrakis(III). S[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] , N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4 -hydroxyphenylpropionamide)], bis-[3,3-bis-(4′-hydro 3'-tert-butylphenyl butanoic acid glycol ester Tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate Thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydro (oxyphenyl)propionate, 3,3',3″,5,5',5″-hexa-tert -Butyl-a,a',a"-(methylene-2,4,6-triyl)tri-p-cresol , hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl ) propionate], tetrakis[methylene-3-(3,5-di-tert-butyl-4 -hydroxyphenyl)propionate]methane, and methylene-3-(3,5-di-t ert-butyl-4-hydroxyphenyl)propionate.
[0079] Examples of phosphorus-based antioxidants include tris(2,4-di-tert-butylphenyl ) Phosphite, Tris[2-[[2,4,8,10-tetra-tert-butylbenzene Zo[d,f][1,3,2]dioxaphosphen-6-yl]oxy]ethyl]a Mine, tetrakis(2,4-di-tert-butylphenyl)[1,1-biphenyl]- 4,4'-diylbisphosphonite, distearyl pentaerythritol diphosphite Bis(2,4-di-tert-butylphenyl)pentaerythritol phosphite , bis(2,6-di-tert-butyl-4-phenyl)pentaerythritol phospha , and bis(2,4-di-tert-butylphenyl)pentaerythritol diphos Fight is one example.
[0080] Examples of ultraviolet absorbers include 2-(2H-benzotriazol-2-yl)-4, 6-Bis(1-methyl-1-phenylethyl)phenol, 2-(2H-benzotriazo (2-yl)-4,6-di-tert-pentylphenol, propanediol and [(4-methoxyphenyl)-methylene]-dimethyl ester.
[0081] Examples of the hindered amine light stabilizer include N,N',N'',N'''-tetrakis(2-methylphenyl)- Su-(4,6-bis-(butyl-(N-methyl-2,2,6,6-tetramethylpiperidine) - 4-yl)amino)-triazin-2-yl)-4,7-diazadecane-1,10- Diamine, poly[(6-(1,1,3,3-tetramethylbutyl)amino-1,3,5- Triazine-2,4-diyl)(2,2,6,6-tetramethyl-4-piperidyl)imide hexamethylene((2,2,6,6-tetramethyl-4-piperidyl)imino) Bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, 2,2,4,4- Tetramethyl-7-oxa-3,20-diazadispiro-[5.1.11.2]-hen Eicosan-21-one, propanedioic acid, [(4-methoxyphenyl)-methylene]-, Bis(1,2,2,6,6-pentamethyl-4-piperidinyl) ester, 1,3-benzo Zenedicarboxamide, N,N-bis(2,2,6,6-tetramethyl-4-piperidinyl) nyl), and 2-ethyl, 2'-ethoxy-oxalanilide.
[0082] The weather resistance additives may be used alone or in combination of two or more. Among them, the weather resistance additive is pentaerythritol tetrakis[3-(3,5-di- tert-Butyl-4-hydroxyphenyl)propionate], N,N'-hexane- 1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl]propane propionamide)], tris(3,5-di-tert-butyl-4-hydroxybenzyl ) isocyanurate, tris(2,4-di-tert-butylphenyl)phosphite , tetrakis(2,4-di-tert-butylphenyl)[1,1-biphenyl]-4, 4'-Diylbisphosphonite, bis(2,4-di-tert-butylphenyl)pentane Taerythritol phosphite, 2-(2H-benzotriazol-2-yl)-4,6 -Bis(1-methyl-1-phenylethyl)phenol, 2-ethyl, 2′-ethoxy- Oxalanilide, N,N',N'',N'''-tetrakis-(4,6-bis-(butyl- (N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)-triazine 2-phenyl-4,7-diazadecane-1,10-diamine, poly[(6-(1,1, 3,3-Tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl)(2 ,2,6,6-tetramethyl-4-piperidyl)imino] hexamethylene ((2,2, 6,6-Tetramethyl-4-piperidylimino), 1,3-benzenedicarboxya and N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl) It is preferable that the compound is one or more selected from the group consisting of the following:
[0083] The functional sustained-release composition of this embodiment has a surface concentration of the liquid component when compressed at 10 MPa or more. 1.0mg / cm 2 It is preferred that the surface concentration is less than 1000 μg / cm 2 That's all. When the functional sustained-release composition is processed by injection molding, etc., the surface becomes sticky, and the like. There is a risk of problems such as clogging with material pellets.
[0084] (Application) The functional sustained-release composition can be used not only by processing it into a molded product having a predetermined shape, but also as it is. It can also be used in its raw form, for example as a paint, sealant, cushioning material or filling. The functional sustained-release composition can be prepared, for example, by selecting an appropriate matrix resin and providing a functional sustained-release The amount of the porous coordination polymer adsorbed with the volatile liquid and the amount of the filler, plasticizer, etc. added are appropriately adjusted. By doing so, a molded article having fluidity, semi-fluidity or rubber-like elasticity can be produced. Therefore, the present invention also includes a molded article made from the functional sustained release composition of the present embodiment. Those with a semi-fluid property can be used as a coating material, for example, and those with a semi-fluid property can be used as a sealant, for example. In addition, rubber-like elasticity can be used as a cushioning material or padding. The functional sustained-release composition can be used as a coating material, a sealant, a cushioning material, or a filling material. When using it as a product, coloring materials such as colorants and pigments can be added to the matrix resin as necessary. In the molding process of the functional sustained-release composition, for example, injection molding, compression molding, etc. Molding, transfer molding, extrusion molding, blow molding, calendar molding, FRP molding, lamination Molding, Casting, Solution Casting, Vacuum and Compressed Air Molding, Extrusion Composite Molding, Foam Molding, Thermoforming, Insulation Any suitable known molding method such as sintering, melt impregnation, etc. may be used. There are no particular limitations on the shape of the product, which may be a flat plate, rod, or cylinder. The functional sustained release composition can be formed into any shape, such as a comb shape, a sphere, etc. In addition to molding, it is also possible to perform two- or multi-color molding in combination with metal or the like. EXAMPLES
[0085] The present invention will be described in detail below using examples and comparative examples. There is no further limitation.
[0086] [Example 1] Etofenprox (melting point 37℃, boiling point 200℃, molecular weight 376.49, Acid dissociation constant 20, Mitsui Chemicals Agro product), porous body containing magnesium ions as metal ions (oxidation number 2, ionic radius 45 pm), composed of 2,5-dihydroxyterephthalic acid as an organic ligand. The porous coordination polymer "MOF-74-Mg" has a specific surface area of 1,200 m2 measured by the BET method. 2 / g, average pore size The functional sustained-release liquid was placed in the porous material so that the composition was as shown in Table 1 below. The adsorption method was as follows: the porous body was placed in a vacuum bell jar and the porous body was The pressure was reduced to 0.01 MPa or less, and Etofenprox was dripped into the porous material. The method used was to use the porous material adsorbing etofenprox as a matrix resin. Compounded with polyethylene resin (Novatec UJ310 made by Nippon Polyethylene Co., Ltd.) The polyethylene resin was processed and mixed to produce a functional sustained release composition (molded body material). The amount is determined by the content of the matrix resin (polyethylene resin), the functional sustained release liquid (etofenp The content of the porous material (porous coordination polymer) and the content of the granular material (granular rocks) are shown in Table 1 below. The compound processing method was a Labo Plastomill device (Toyo Seiki Co., Ltd.). The compounding was performed at a processing temperature of 120°C for 10 minutes. Using a press machine (Imoto Manufacturing's "IMC180C type"), the compact material was pressurized at 120°C for 5 tons. The mixture was pressed to prepare a plate molded body having a size of 50 mm×50 mm and a thickness of 1.2 mm.
[0087] Regarding Table 1 below. *Exponential function formula: y (surface amount of functional sustained release liquid), x (repetition rate) A (initial value of the surface amount of the functional sustained-release liquid), B (repeated washing and functional sustained-release liquid The magnitude of change in the surface area of the material is expressed as the surface area of the material. [Table 1]
[0088] [Example 2] The metal ion is aluminum ion (oxidation number 3, ionic radius 54 pm), and the organic ligand is A porous coordination polymer composed of fumaric acid ("Al-PCP-F"), specific surface area by BET method: 900 m 2 A functional sustained-release composition (composition: 1 / g, average pore size: 0.6 nm) was used in the same manner as in Example 1. The amount of polyethylene resin blended was 1:1. Resin) content, functional sustained release liquid (etofenprox) content and porous body (porous The contents of the respective polymers (polymers having a crystalline structure and a crystalline coordination polymer) were adjusted to the amounts shown in Table 1. In the same manner as in Example 1, a compact was produced from each compact material, and this was designated Example 2.
[0089] [Example 3] The metal ion is iron ion (oxidation number 3, ionic radius 55 pm), and the organic ligand is trimesium. A porous coordination polymer composed of phosphate (Fe-BTC, specific surface area by BET method: 1,754 m 2 / g The functional sustained-release composition (composition: 1) was prepared in the same manner as in Example 1, except that a pore size of 1.5 mm or less was used. The amount of polyethylene resin blended was 1:1. Resin) content, functional sustained release liquid (etofenprox) content and porous body (porous The contents of the respective polymers (polymers having a crystalline structure and a crystalline coordination polymer) were adjusted to the amounts shown in Table 1. In the same manner as in Example 1, a compact was produced from each compact material, and this was designated Example 3.
[0090] [Example 4] The metal ion is chromium ion (oxidation number 3, ionic radius 63 pm), and the organic ligand is terephthalic acid. Porous coordination polymer composed of phthalic acid ("MIL-101(Cr)", BET surface area: 2,20 0 m 2 The functional sustained-release composition was prepared in the same manner as in Example 1, except that a 100% cellulose acetate stearate solution was used (1.0 g / g, average pore size: 2.0 to 2.7 nm). The amount of polyethylene resin blended was determined by the matrix resin (polyethylene The content of functional sustained release liquid (etofenprox) and the porous body The amount of (porous coordination polymer) was adjusted to be as shown in Table 1. In the same manner as in Example 1, a compact was produced from each compact material, and this was designated as Example 4.
[0091] [Example 5] Nickel ion (oxidation number 1, ionic radius 68 pm) as metal ion, 2,5 as organic ligand -Porous coordination polymer composed of dihydroxyterephthalic acid ("MOF-74-Ni"), using the BET method Surface area: 1,360 m 2 The same procedure was carried out as in Example 1, except that a 1.0 μm / g pore size and average pore size of 1.0 nm were used. The amount of polyethylene resin blended was 100%. Resin (polyethylene resin) content, functional sustained-release liquid (etofenprox) content and the amount of the porous body (porous coordination polymer) is set to be as shown in Table 1. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, and this was designated as Example 5. Ta.
[0092] [Example 6] The metal ion is zirconium ion (oxidation number 4, ionic radius 72 pm), and the organic ligand is A porous coordination polymer composed of terephthalic acid (Uio-66, surface area by BET method: 1.0 00 m 2 A functional sustained-release composition ( The amount of polyethylene resin blended was 100%. The content of functional sustained release liquid (etofenprox) and porous body (poly The amount of each of the porous coordination polymers was adjusted so that the content of each of the porous coordination polymers was as shown in Table 1. In the same manner as in Example 1, a compact was produced from each of the compact materials, and this was designated as Example 6.
[0093] [Example 7] The metal ion is copper ion (oxidation number 2, ionic radius 73 pm), and the organic ligand is trimesium. A porous coordination polymer composed of phosphate (Cu-BTC, BET surface area: 1,500 m 2 / g, The functional sustained-release composition (molded body material: 0.9 nm) was used in the same manner as in Example 1, except that The amount of polyethylene resin blended was 1:1. Content, functional sustained release liquid (etofenprox) content and porous body (porosity coordination high The amount of each of the molecules was adjusted to be as shown in Table 1. A compact was produced from each of the compact materials, which was designated as Example 7.
[0094] [Example 8] The metal ion is zinc ion (oxidation number 2, ionic radius 74 pm), and the organic ligand is 2-methyl A porous coordination polymer composed of lumidazole ("ZIF-8", BET surface area: 1,40 0 m 2 The functional sustained-release composition was prepared in the same manner as in Example 1, except that a 100% cellulose acetate stearate solution was used (0.3 to 1.1 nm). The amount of polyethylene resin blended was determined by the matrix resin (polyethylene The content of functional sustained release liquid (etofenprox) and the porous body The amount of (porous coordination polymer) was adjusted to be as shown in Table 1. A compact was produced from each compact material in the same manner as in Example 1, and this was designated Example 8.
[0095] [Example 9] Functional sustained release liquid: 2-n-octyl-4-isothiazolin-3-one (melting point 23°C, boiling point 142°C) , molecular weight 213.34, acid dissociation constant -0.23, Tokyo Chemical Industry Co., Ltd. product), as a porous material, it is highly soluble in metal ions Nickel ion (oxidation number 1, ionic radius 68 pm), 2,5-dihydroxyterephthalic acid as an organic ligand Porous coordination polymer composed of phthalic acid ("MOF-74-Ni", BET surface area: 1,360 m 2 / g, average pore size: 1.0 nm), ethylene vinyl acetate resin (Asahi Kasei) as matrix resin The functional sustained-release composition ( The amount of ethylene vinyl acetate resin blended was 100% of the matrix resin (ethylene vinyl acetate). Content of vinyl acetate resin, functional sustained release liquid (2-n-octyl-4-isothiazoline-3-ol The content of the porous body (porous coordination polymer) is as shown in Table 2 below. After that, a compact was produced from each compact material in the same manner as in Example 1, and This was designated as Example 9.
[0096] Regarding Table 2 below. *Exponential function formula: y (surface amount of functional sustained release liquid), x (repeated washing A (initial value of the surface amount of the functional sustained-release liquid), B (repeated washing and the surface amount of the functional sustained-release liquid) It is expressed as the magnitude of change in surface area. [Table 2]
[0097] [Example 10] The metal ion is zirconium ion (oxidation number 4, ionic radius 72 pm), and the organic ligand is A porous coordination polymer composed of terephthalic acid (Uio-66, surface area by BET method: 1.0 00 m 2 A functional sustained-release composition ( The amount of ethylene vinyl acetate resin blended was 100% of the matrix resin (ethylene vinyl acetate). Content of vinyl acetate resin, functional sustained release liquid (2-n-octyl-4-isothiazoline-3-ol The content of the porous body (porous coordination polymer) is as shown in Table 2. After that, a compact was produced from each compact material in the same manner as in Example 1, and This was designated as Example 10.
[0098] [Example 11] The metal ion is copper ion (oxidation number 2, ionic radius 73 pm), and the organic ligand is trimesium. A porous coordination polymer composed of phosphate (Cu-BTC, BET surface area: 1,500 m 2 / g, The functional sustained-release composition (molded body material: 0.9 nm) was used in the same manner as in Example 9, except that The amount of ethylene vinyl acetate resin was 100% of the matrix resin (ethylene vinyl acetate). Content of functional sustained release liquid (2-n-octyl-4-isothiazolin-3-one) The amount of the porous material (porous coordination polymer) and the amount of the porous material (porous coordination polymer) are as shown in Table 2. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, and this was used as Example 11. It was decided.
[0099] [Example 12] The metal ion is zinc ion (oxidation number 2, ionic radius 74 pm), and the organic ligand is 2-methyl A porous coordination polymer composed of lumidazole ("ZIF-8", BET surface area: 1,40 0 m 2 A functional sustained-release composition was prepared in the same manner as in Example 9, except that a 100% cellulose acetate stearate solution was used (0.3 to 1.1 nm). The amount of ethylene vinyl acetate resin was adjusted to the matrix resin ( Ethylene vinyl acetate resin) content, functional sustained release liquid (2-n-octyl-4-isothiazoline- The content of the 3-one and the content of the porous body (porous coordination polymer) are shown in Table 2. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, This was designated as Example 12.
[0100] [Example 13] The metal ion is sodium ion (oxidation number 1, ionic radius 103 pm), and the ligand is aluminum. Zeolite composed of minosilicate (Union Showa's "USKY-790", table by BET method) Area: 792 m 2 The same procedure as in Example 9 was repeated except that a 0.5 nm / g pore size was used. The composition (molded body material) was prepared. The amount of ethylene vinyl acetate resin was Content of fat (ethylene vinyl acetate resin), functional sustained release liquid (2-n-octyl-4-isothiazo The content of phosphorus-3-one and the content of porous material (zeolite) are shown in Table 2. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, This was designated as Example 13.
[0101] [Example 14] The metal ion is silver ion (oxidation number 1, ionic radius 115 pm), and the ligand is di-p-xylylene. The same procedure as in Example 9 was used except that a porous coordination polymer composed of ethylene ("Ag-PCP") was used. The amount of ethylene vinyl acetate resin was 100%. Content of trix resin (ethylene vinyl acetate resin), functional sustained release liquid (2-n-octyl-4 -isothiazolin-3-one) content and porous body (zeolite) content are respectively The amounts were as shown in Table 2. Thereafter, in the same manner as in Example 1, each of the compact materials was mixed to produce a compact. This was designated as Example 14.
[0102] [Example 15] Methyl anthranilate (melting point 24°C, boiling point 256°C, molecular weight 151.16, Acid dissociation constant 2.23, Tokyo Chemical Industry product), nickel ion (acid) in metal ion as a porous material The compound has a chemical number of 1 and an ionic radius of 68 pm, and is composed of 2,5-dihydroxyterephthalic acid as an organic ligand. The porous coordination polymer "MOF-74-Ni" has a BET surface area of 1,360 m 2 / g, average pore size : 1.0 nm), and polypropylene resin as the matrix resin (Prime Polymer's "Prime Polymer" The functional sustained-release composition (molded body) was prepared in the same manner as in Example 1, except that "Lime Polypro J105G" was used. The amount of polypropylene resin blended was 1:1. Resin) content, functional sustained release liquid (methyl anthranilate) content and porous body (porous The contents of the respective polymers (polymers having a crystalline structure and a crystalline coordination polymer) were adjusted to the amounts shown in Table 3 below. In the same manner as in Example 1, a compact was produced from each compact material, and this was designated Example 15.
[0103] Regarding Table 3 below. *Exponential function formula: y (surface amount of functional sustained release liquid), x (repeated washing A (initial value of the surface amount of the functional sustained-release liquid), B (repeated washing and the surface amount of the functional sustained-release liquid) It is expressed as the magnitude of change in surface area. [Table 3]
[0104] [Example 16] The metal ion is zirconium ion (oxidation number 4, ionic radius 72 pm), and the organic ligand is A porous coordination polymer composed of terephthalic acid (Uio-66, surface area by BET method: 1.0 00 m 2 A functional sustained-release composition was prepared in the same manner as in Example 15, except that a 100% cellulose acetate stearate solution was used (0.9 nm / g, average pore size: 0.9 nm). The amount of polypropylene resin blended was 100% of the matrix resin (polypropylene). propylene resin), functional sustained release liquid (methyl anthranilate) content and porous The amount of the porous coordination polymer was adjusted so that the content of the porous coordination polymer was as shown in Table 3. A compact was produced from each compact material in the same manner as in Example 1, and this was designated Example 16.
[0105] [Example 17] The metal ion is copper ion (oxidation number 2, ionic radius 73 pm), and the organic ligand is trimesium. A porous coordination polymer composed of phosphate (Cu-BTC, BET surface area: 1,500 m 2 / g, The functional sustained-release composition (molded body material: average pore size: 0.9 nm) was used in the same manner as in Example 15, except that The amount of polypropylene resin blended was 100%. fat), functional sustained-release liquid (methyl anthranilate) content and porous body (porous The contents of the coordination polymers were adjusted to the amounts shown in Table 3. In the same manner as described above, a compact was produced from each of the compact materials, and this was designated Example 17.
[0106] [Example 18] The metal ion is zinc ion (oxidation number 2, ionic radius 74 pm), and the organic ligand is 2-methyl A porous coordination polymer composed of lumidazole ("ZIF-8", BET surface area: 1,40 0 m 2 The functional sustained-release composition was prepared in the same manner as in Example 15, except that the pore size was 0.3 to 1.1 nm. The amount of polypropylene resin blended was 100%. Polypropylene resin) content, functional sustained release liquid (methyl anthranilate) content and The amount of the porous body (porous coordination polymer) was determined so that the content of each was as shown in Table 3. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, and this was designated Example 18.
[0107] [Example 19] The metal ion is sodium ion (oxidation number 1, ionic radius 103 pm), and the ligand is aluminum. Zeolite composed of minosilicate (Union Showa's "USKY-790", table by BET method) Area: 792 m 2 The same procedure as in Example 15 was repeated except that a 0.5 nm / g pore size and an average pore size of 0.5 nm were used. A composition (molded body material) was prepared. The amount of polypropylene resin blended was 100% of the matrix resin ( Polypropylene resin) content, functional sustained release liquid (methyl anthranilate) content and The amount of the porous material (zeolite) was adjusted so that the content of each was as shown in Table 3. A compact was produced from each compact material in the same manner as in Example 1, and this was designated Example 19.
[0108] [Example 20] The metal ion is silver ion (oxidation number 1, ionic radius 115 pm), and the ligand is di-p-xylylene. The same procedure as in Example 15 was used except that a porous coordination polymer composed of ethylene ("Ag-PCP") was used. The amount of polypropylene resin blended was 100%. Content of styrene resin (polypropylene resin), functional sustained release liquid (methyl anthranilate) The content of the porous body (zeolite) is as shown in Table 3. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, and this was used as Example 20. It was decided.
[0109] [Example 21] Functional sustained release liquid: 5-heptyloxolan-2-one (melting point 164°C, boiling point 286°C, molecular weight 1 84.27, acid dissociation constant 12.87, pure chemical product), magnesium ion as a porous material ion (oxidation number 2, ionic radius 45 pm), composed of 2,5-dihydroxyterephthalic acid as an organic ligand. The porous coordination polymer (MOF-74-Mg, specific surface area measured by BET method: 1,200 m 2 / g, average The functional sustained-release composition (molded body material) was prepared in the same manner as in Example 15, except that a pore size of 1.1 nm was used. The amount of polypropylene resin blended was 1:1. The content of functional sustained release liquid (5-heptyloxolan-2-one) and the carrier (porous The contents of the respective polymers (polymers having a crystalline structure and a crystalline coordination polymer) were adjusted to the amounts shown in Table 4 below. In the same manner as in Example 1, a compact was produced from each compact material, and this was designated Example 21.
[0110] Regarding Table 4 below. *Exponential function formula: y (surface amount of functional sustained release liquid), x (repeated washing A (initial value of the surface amount of the functional sustained-release liquid), B (repeated washing and the surface amount of the functional sustained-release liquid) It is expressed as the magnitude of change in surface area. [Table 4]
[0111] [Example 22] Metal ions include aluminum ion (oxidation number 3, ionic radius 54 pm), A porous coordination polymer consisting of fumaric acid as an organic ligand ("Al-PCP-F"), a comparison table by the BET method Area: 900 m 2 The same procedure as in Example 21 was repeated except that a 0.1% cellulose acetate syrup was used (average pore size: 0.6 nm). A composition (molded body material) was prepared. The amount of polypropylene resin blended was 100% of the matrix resin ( Polypropylene resin) content, functional sustained release liquid (5-heptyloxolan-2-one) content The amount of the support (porous coordination polymer) and the amount of the catalyst are as shown in Table 4. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, and this was used as Example 22. It was decided.
[0112] [Example 23] The metal ion is iron ion (oxidation number 3, ionic radius 55 pm), and the organic ligand is trimesium. Porous coordination polymer composed of phosphate (Fe-BTC, specific surface area by BET method: 1,754 m 2 / g, A functional sustained-release composition (molded The amount of polypropylene resin blended was 100%. Content of functional sustained release liquid (5-heptyloxolan-2-one) and its loading The amount of the porous coordination polymer was adjusted so that the content of the porous coordination polymer was as shown in Table 4. A compact was produced from each compact material in the same manner as in Example 1, and this was designated Example 23.
[0113] [Example 24] The metal ion is chromium ion (oxidation number 3, ionic radius 63 pm), and the organic ligand is terephthalic acid. Porous coordination polymer composed of phthalic acid ("MIL-101", BET surface area: 2,200 m 2 A functional sustained-release composition was prepared in the same manner as in Example 21, except that a 100% cellulose acetate stearate solution was used (1.0 g / g, average pore size: 2.0 to 2.7 nm). The amount of polypropylene resin blended was 100% of the matrix resin (polypropylene). propylene resin), functional sustained release liquid (5-heptyloxolan-2-one) content and The amounts of the support (porous coordination polymer) and the catalyst were adjusted so that the contents thereof were as shown in Table 4 above. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, and this was designated as Example 24. .
[0114] [Example 25] Nickel ion (oxidation number 1, ionic radius 68 pm) as metal ion, 2,5 as organic ligand -Porous coordination polymer composed of dihydroxyterephthalic acid ("MOF-74-Ni"), using the BET method Surface area: 1,360 m 2 The same procedure as in Example 21 was repeated except that a pore size of 1.0 μm / g and an average pore size of 1.0 nm were used. The amount of polypropylene resin blended was 100%. Resin content (polypropylene resin), functional sustained release liquid (5-heptyloxolane-2-ol The content of the support (porous coordination polymer) is as shown in Table 4. Thereafter, a compact was prepared from each of the compact materials in the same manner as in Example 1, and This was Example 25.
[0115] [Example 26] The metal ion is zirconium ion (oxidation number 4, ionic radius 72 pm), and the organic ligand is A porous coordination polymer composed of terephthalic acid (Uio-66, surface area by BET method: 1.0 00 m 2 A functional sustained-release composition was prepared in the same manner as in Example 21, except that a 100% cellulose acetate stearate solution was used (0.9 nm / g, average pore size: 0.9 nm). The amount of polypropylene resin blended was 100% of the matrix resin (polypropylene). propylene resin), functional sustained release liquid (5-heptyloxolan-2-one) content and The amounts of the support (porous coordination polymer) and the catalyst were adjusted so that the contents thereof were as shown in Table 4 above. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, and this was designated as Example 26. .
[0116] [Example 27] The metal ion is copper ion (oxidation number 2, ionic radius 73 pm), and the organic ligand is trimesium. Porous coordination polymer (Cu-BTC) composed of phosphate, BET surface area: 1,500 m 2 / g, flat The functional sustained-release composition (molded body material: 0.9 nm) was used in the same manner as in Example 21, except that The amount of polypropylene resin was adjusted to the matrix resin (polypropylene resin ), functional sustained release liquid (5-heptyloxolan-2-one) content and carrier (multiple The amount of each of the porous coordination polymers was adjusted to be as shown in Table 4. In the same manner as in Example 1, a molded body was produced from each molded body material, and this was designated as Example 27.
[0117] [Example 28] The metal ion is zinc ion (oxidation number 2, ionic radius 74 pm), and the organic ligand is 2-methyl A porous coordination polymer composed of lumidazole ("ZIF-8", BET surface area: 1,40 0 m 2 The functional sustained-release composition was prepared in the same manner as in Example 21, except that a 100% cellulose acetate stearate solution was used (0.3 to 1.1 nm, average pore size: 0.3 to 1.1 nm). The amount of polypropylene resin blended was 100%. Polypropylene resin) content, functional sustained release liquid (5-heptyloxolan-2-one) content The amount of the support (porous coordination polymer) is set to be as shown in Table 4. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, and this was designated as Example 28. did.
[0118] [Example 29] The metal ion is sodium ion (oxidation number 1, ionic radius 103 pm), and the ligand is aluminum. Zeolite composed of minosilicate (Union Showa's "USKY-790", table by BET method) Area: 792 m 2 The same procedure as in Example 21 was repeated except that a 0.5 nm / g pore size was used. A composition (molded body material) was prepared. The amount of polypropylene resin blended was 100% of the matrix resin ( Polypropylene resin) content, functional sustained release liquid (5-heptyloxolan-2-one) content The amount of the support (porous coordination polymer) and the amount of the catalyst are as shown in Table 4. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, and this was used as Example 29. It was decided.
[0119] [Example 30] The metal ion is silver ion (oxidation number 1, ionic radius 115 pm), and the ligand is di-p-xylylene. The same procedure as in Example 21 was carried out except that a porous coordination polymer composed of ethylene ("Ag-PCP") was used. The amount of polypropylene resin blended was 100%. Content of oxalic acid resin (polypropylene resin), functional sustained release liquid (5-heptyloxolane-2 The content of the support (porous coordination polymer) is as shown in Table 4. After that, a compact was produced from each compact material in the same manner as in Example 1. This was designated as Example 30.
[0120] [Example 31] Chlorpyrifos (melting point 41°C, boiling point 160°C, molecular weight 350.58, acid dissociation) as functional sustained release liquid Constant -5.28, Fujifilm Wako Pure Chemical products), sodium ions are added to metal ions as a porous material Zeolaran (oxidation state 1, ionic radius 103 pm) and aluminosilicate as ligand. Thread (Union Showa's "USKY-790"), surface area by BET method: 792 m 2 / g, average pore size: 0.5n A functional sustained-release composition (molded body material) was prepared in the same manner as in Example 21, except that the compound (I) was used. The amount of polypropylene resin blended depends on the content of the matrix resin (polypropylene resin), the The content of the active sustained-release liquid (chlorpyrifos) and the content of the carrier (porous coordination polymer) are The amounts of each were as shown in Table 5 below. Then, in the same manner as in Example 1, each of the compact materials was A molded body was produced from the above, which was designated as Example 31.
[0121] Regarding Table 5 below. *Exponential function formula: y (surface amount of functional sustained release liquid), x (repeated washing A (initial value of the surface amount of the functional sustained-release liquid), B (repeated washing and the surface amount of the functional sustained-release liquid) It is expressed as the magnitude of change in surface area. [Table 5]
[0122] [Example 32] The metal ion is silver ion (oxidation number 1, ionic radius 115 pm), and the ligand is di-p-xylylene. The same procedure as in Example 31 was carried out except that a porous coordination polymer composed of arylene ("Ag-PCP") was used. The amount of polypropylene resin blended was 100%. Content of ethylene resin (polypropylene resin), content of functional sustained release liquid (chlorpyrifos) The amount of the support (porous coordination polymer) and the amount of the sintered material are as shown in Table 5. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, and this was used as Example 32. It was decided.
[0123] [Example 33] Dimethyl sulfoxide (melting point 19°C, boiling point 189°C, molecular weight 78.13, acid) as functional sustained release liquid Dissociation constant 33, Fujifilm Wako Pure Chemical products), magnesium ion is attached to metal ions as a porous material ion (oxidation number 2, ionic radius 45 pm), composed of 2,5-dihydroxyterephthalic acid as an organic ligand. The porous coordination polymer (MOF-74-Mg, specific surface area measured by BET method: 1,200 m 2 / g, average The functional sustained-release composition (molded body material) was prepared in the same manner as in Example 31, except that a pore size of 1.1 nm was used. The amount of polypropylene resin blended was 1:1. The content of functional sustained release liquid (dimethyl sulfoxide) and the support (porous coordination high The amount of each of the molecules was adjusted to be as shown in Table 6 below. A compact was then produced from each of the compact materials, which was designated as Example 33.
[0124] Regarding Table 6 below. *Exponential function formula: y (surface amount of functional sustained release liquid), x (repeated washing A (initial value of the surface amount of the functional sustained-release liquid), B (repeated washing and the surface amount of the functional sustained-release liquid) It is expressed as the magnitude of change in surface area. [Table 6]
[0125] [Example 34] Metal ions include aluminum ion (oxidation number 3, ionic radius 54 pm), A porous coordination polymer consisting of fumaric acid as an organic ligand ("Al-PCP-F"), a comparison table by the BET method Area: 900 m 2 The same procedure as in Example 33 was repeated except that a 0.1% cellulose acetate syrup was used (average pore size: 0.6 nm). A composition (molded body material) was prepared. The amount of polypropylene resin blended was 100% of the matrix resin ( Polypropylene resin) content, functional sustained release liquid (dimethyl sulfoxide) content and The amount of the support (porous coordination polymer) was adjusted so that the content was as shown in Table 6. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, and this was designated Example 34.
[0126] [Example 35] The metal ion is iron ion (oxidation number 3, ionic radius 55 pm), and the organic ligand is trimesium. A porous coordination polymer composed of phosphate (Fe-BTC, specific surface area by BET method: 1,754 m 2 / g The functional sustained-release composition (composition: 1.0 to 1.2 nm) was prepared in the same manner as in Example 33, except that a 1.0 to 1.2 nm pore size (average pore size: 2.4 to 2.9 nm) was used. The amount of polypropylene resin blended was 100%. Content of functional sustained release liquid (dimethyl sulfoxide) and carrier (polyethylene resin) The amount of each of the porous coordination polymers was adjusted to be as shown in Table 6. In the same manner as in Example 1, a molded body was produced from each molded body material, and this was designated as Example 35.
[0127] [Example 36] The metal ion is chromium ion (oxidation number 3, ionic radius 63 pm), and the organic ligand is terephthalic acid. Porous coordination polymer composed of phthalic acid ("MIL-101", BET surface area: 2,200 m 2 A functional sustained-release composition was prepared in the same manner as in Example 33, except that a 100% cellulose acetate stearate solution was used (1.0 g / g, average pore size: 2.0 to 2.7 nm). The amount of polypropylene resin blended was 100% of the matrix resin (polypropylene). propylene resin), functional sustained release liquid (dimethyl sulfoxide) content and carrier The amount of (porous coordination polymer) was adjusted to be as shown in Table 6. A molded body was produced from each molded body material in the same manner as in Example 1, and this was designated as Example 36.
[0128] [Example 37] Nickel ion (oxidation number 1, ionic radius 68 pm) as metal ion, 2,5 as organic ligand -Porous coordination polymer composed of dihydroxyterephthalic acid ("MOF-74-Ni"), using the BET method Surface area: 1,360 m 2 The same procedure as in Example 33 was carried out except that a 1.0 μm / g pore size and average pore size of 1.0 nm were used. The amount of polypropylene resin blended was 100%. Content of polypropylene resin, content of functional sustained release liquid (dimethyl sulfoxide) The amount of the support (porous coordination polymer) and the amount of the catalyst are as shown in Table 6. Thereafter, a compact was produced from each compact material in the same manner as in Example 1, and this was used as Example 37. It was decided.
[0129] [Comparative Example 1-1] The etofenprox used in Example 1 as the functional sustained-release liquid was mixed with a matrix resin. Compounding with polyethylene resin (LDPE without polar group or functional group modification) The amount of polyethylene resin was 100%. The content of the polyethylene resin and the content of the functional sustained release liquid are shown in Table 1. The amount was set as shown. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having dimensions of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 1.
[0130] [Comparative Example 1-2] The etofenprox used in Example 1 was used as the functional sustained-release liquid, and sodium was used as the metal ion. Consists of thorium ion (oxidation state 1, ionic radius 103 pm) and aluminosilicate as ligand The zeolite used (Union Showa's "USKY-790") has a BET surface area of 792 m 2 / g, average Pore size: 0.5 nm) and polyethylene resin (polar group and functional group modified) as matrix resin. The composition (molded body material) was prepared by compounding and mixing with LDPE (not subjected to the above process). The amount of polyethylene resin blended depends on the content of the matrix resin (polyethylene resin) and the functionality. Content of sustained-release liquid (etofenprox) and porous body (porous coordination polymer) The amounts were set as shown in Table 1 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 1-2.
[0131] [Comparative Example 1-3] The functional sustained-release liquid was the etofenprox used in Example 1, and the metal ion was silver. ion (oxidation number 1, ionic radius 115 pm), and a polycyclic compound consisting of di-p-xylylene as a ligand. A porous coordination polymer ("Ag-PCP") is used as the matrix resin, and polyethylene resin (polar groups and The composition (molded body material) is compounded and mixed with LDPE (which has not been modified with functional groups). The amount of polyethylene resin blended was 1:1. Content, functional sustained release liquid (etofenprox) content and porous body (porosity coordination high The amounts were adjusted so that the contents of each of the molecules were as shown in Table 1 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated as Comparative Example 1-3.
[0132] [Comparative Example 2-1] The functional sustained-release liquid 2-n-octyl-4-isothiazolin-3-one used in Example 9 was Ethylene vinyl acetate resin (Asahi Kasei's "Suntech EM6415") as a trix resin The mixture was compounded and mixed to prepare a composition (material for molding). The amount of fat blended depends on the content of matrix resin (vinyl acetate resin) and the content of functional sustained release liquid. The amounts were adjusted so that the contents were as shown in Table 2 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having dimensions of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 2-1.
[0133] [Comparative Example 2-2] The functional sustained-release liquid used in Example 9 was 2-n-octyl-4-isothiazolin-3-one, which was then mixed with gold The group ion is magnesium ion (oxidation number 2, ionic radius 45 pm), and the organic ligand is 2,5-diamine. Porous coordination polymer composed of hydroxyterephthalic acid ("MOF-74-Mg"), prepared by the BET method Specific surface area: 1,200 m 2 / g, average pore size: 1.1 nm) was used as the matrix resin, and ethylene acetate was used as the matrix resin. Compounding and mixing with vinyl resin (Asahi Kasei's "Suntech EM6415") to form the composition The amount of ethylene vinyl acetate resin was adjusted to the matrix resin ( Vinyl acetate resin) content, functional sustained release liquid (2-n-octyl-4-isothiazoline-3-ol The content of the porous body (porous coordination polymer) is as shown in Table 2. The amount was set to be: The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 2-2.
[0134] [Comparative Example 2-3] The functional sustained-release liquid used in Example 9 was 2-n-octyl-4-isothiazolin-3-one, which was then mixed with gold The group ion is aluminum ion (oxidation number 3, ionic radius 54 pm), and the organic ligand is fumaric acid. A porous coordination polymer ("Al-PCP-F") composed of Al-PCP and Al-PCP-F, specific surface area by BET method: 900 m 2 / g, average Pore size: 0.6 nm) and ethylene vinyl acetate resin (Asahi Kasei product) as the matrix resin. "Suntech EM6415") is compounded and mixed to prepare a composition (molded body material). The amount of ethylene vinyl acetate resin was determined based on the amount of matrix resin (vinyl acetate resin). Content, functional sustained release liquid (2-n-octyl-4-isothiazolin-3-one) content and porous body The contents of the (porous coordination polymer) were adjusted to be those shown in Table 2 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated as Comparative Example 2-3.
[0135] [Comparative Example 2-4] The functional sustained-release liquid used in Example 9 was 2-n-octyl-4-isothiazolin-3-one, which was then mixed with gold The group ion is iron ion (oxidation number 3, ionic radius 55 pm), and the organic ligand is trimesic acid. A porous coordination polymer composed of Fe-BTC (specific surface area by BET method: 1,754 m 2 / g, flat The average pore size was 2.4 to 2.9 nm, and ethylene vinyl acetate resin (Asahi Kasei) was used as the matrix resin. The compound is processed and mixed with the product "Suntech EM6415" to create a composition (molded body material). The amount of ethylene vinyl acetate resin was 100% of the matrix resin (vinyl acetate resin). The content of functional sustained release liquid (2-n-octyl-4-isothiazolin-3-one) and porous The contents of the porous bodies (porous coordination polymers) were adjusted to the amounts shown in Table 2 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 2-4.
[0136] [Comparative Example 2-5] The functional sustained-release liquid used in Example 9 was 2-n-octyl-4-isothiazolin-3-one, which was then mixed with gold The group ion is chromium ion (oxidation number 3, ionic radius 63 pm), and the organic ligand is terephthalic acid. Porous coordination polymer composed of cyclic acid ("MIL-101(Cr)"), surface area by BET method: 2,200 m 2 / g, average pore size: 2.0-2.7 nm) and ethylene vinyl acetate resin ( Asahi Kasei's "Suntech EM6415" is compounded and mixed to produce a composition (molded body). The amount of ethylene vinyl acetate resin blended was 100%. Resin) content, Functional sustained release liquid (2-n-octyl-4-isothiazolin-3-one) content and the amount of the porous body (porous coordination polymer) is set to be as shown in Table 2. Ta. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 2-5.
[0137] [Comparative Example 3-1] Methyl anthranilate, which was used in Example 15 as a functional sustained-release liquid, was used as a matrix resin. Polypropylene resin (Prime Polymer product "Prime Polypro J105G") is used as the component. The mixture was pounded and mixed to produce a composition (molded body material). The amount of the matrix resin (polypropylene resin) and the functional sustained release liquid are The amounts were as shown in Table 3 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having dimensions of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 3-1.
[0138] [Comparative Example 3-2] Methyl anthranilate used in Example 15 was used as the functional sustained-release liquid, and methyl methacrylate was used as the metal ion. Magnesium ion (oxidation number 2, ionic radius 45 pm), 2,5-dihydroxyterephthalic acid as organic ligand Porous coordination polymer composed of tartaric acid ("MOF-74-Mg", specific surface area by BET method: 1,200 m 2 / g, average pore size: 1.1 nm) and polypropylene resin (prime The polymer product "Prime Polypro J105G" is compounded and mixed to form the composition ( The amount of polypropylene resin blended was 100%. pyrene), functional sustained release liquid (methyl anthranilate) and porous body (poly The contents of the porous coordination polymers were adjusted to be as shown in Table 3 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having dimensions of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 3-2.
[0139] [Comparative Example 3-3] Methyl anthranilate, which was used as the functional sustained-release liquid in Example 15, was converted to aluminum as a metal ion. A porous structure composed of nium ion (oxidation number 3, ionic radius 54 pm) and fumaric acid as an organic ligand. A water-soluble coordination polymer (Al-PCP-F, specific surface area by BET method: 900 m 2 / g, average pore diameter: 0.6nm) The matrix resin is polypropylene resin (Prime Polymer product "PrimePo The composition (molded body material) was prepared by compounding and mixing with the "Repro J105G" resin. The amount of polypropylene resin blended depends on the content of the matrix resin (polypropylene) and the functional sustained release The content of the reactive liquid (methyl anthranilate) and the content of the porous body (porous coordination polymer) The amounts were as shown in Table 3 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 3-3.
[0140] [Comparative Example 3-4] The functional sustained-release liquid was methyl anthranilate, which was used in Example 15, and the metal ion was iron. Polyamine consisting of an ion (oxidation number 3, ionic radius 55 pm) and trimesic acid as an organic ligand. Porous coordination polymer (Fe-BTC, specific surface area by BET method: 1,754 m 2 / g, average pore size: 2.4~2 0.9nm) as the matrix resin, and polypropylene resin (Prime Polymer's "Pla The composition (molded body material) was prepared by compounding and mixing with "Immunopolypro J105G" The amount of polypropylene resin blended depends on the content of the matrix resin (polypropylene), the function, and the The content of active sustained-release liquid (methyl anthranilate) and the content of porous body (porous coordination polymer) The amounts were adjusted so that the contents were as shown in Table 3 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 3-4.
[0141] [Comparative Example 3-5] Methyl anthranilate used in Example 15 was used as the functional sustained release liquid, and chlorine was used as the metal ion. It is composed of a chromium ion (oxidation number 3, ionic radius 63 pm) and terephthalic acid as an organic ligand. A porous coordination polymer ("MIL-101(Cr)") with a BET surface area of 2,200 m 2 / g, average pore size : 2.0 to 2.7 nm) and polypropylene resin (Prime Polymer product) as the matrix resin. "Prime Polypro J105G") is compounded and mixed to produce the composition (molded body material). The amount of polypropylene resin blended was determined based on the content of the matrix resin (polypropylene). The amount of functional sustained release liquid (methyl anthranilate) and the amount of porous material (porous coordination polymer) The amounts of the components (atomic weight) and (oxygen) were adjusted so that the contents thereof were as shown in Table 3 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 3-5.
[0142] [Comparative Example 4] The functional sustained-release liquid used in Example 21 was 5-heptyloxolan-2-one, which was added to the matrix. Polypropylene resin (Prime Polymer product "Prime Polypro J105G") is used as the base resin. The polypropylene resin was compounded and mixed to prepare a composition (molded body material). The amount of fat blended depends on the content of matrix resin (polypropylene resin) and the content of functional sustained release liquid. The amounts were adjusted so that the contents were as shown in Table 4 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 4.
[0143] [Comparative Example 5-1] The functional sustained release liquid was chlorpyrifos, which was used in Example 31, and the matrix resin was polyvinyl chloride. Compounding with polypropylene resin (Prime Polymer product "Prime Polypro J105G") The mixture was processed and mixed to prepare a composition (molded body material). The amount of polypropylene resin was: The matrix resin (polypropylene resin) content and the functional sustained-release liquid content are The amounts were as shown in Table 5 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated as Comparative Example 5-1.
[0144] [Comparative Example 5-2] The functional sustained-release liquid was chlorpyrifos, which was used in Example 31, and magnesium as the metal ion. Umium ion (oxidation number 2, ionic radius 45 pm), organic ligand is 2,5-dihydroxyterephthalic acid A porous coordination polymer (MOF-74-Mg, specific surface area by BET method: 1,200 m 2 / g , average pore size: 1.1 nm) and polypropylene resin (prime poly) as the matrix resin. The compound is processed and mixed with the "Prime Polypro J105G" of the mer product, and the composition (molding The amount of polypropylene resin blended was 100%. The content of functional sustained release liquid (chlorpyrifos) and the porous body (porous coordination high The amounts were adjusted so that the contents of each of the molecules were as shown in Table 5 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 5-2.
[0145] [Comparative Example 5-3] The chlorpyrifos used in Example 31 as the functional sustained-release liquid was added to the metal ion, aluminum. Porous coordination consisting of ions (oxidation number 3, ionic radius 54 pm) and fumaric acid as organic ligands Polymer ("Al-PCP-F", specific surface area by BET method: 900m 2 / g, average pore size: 0.6 nm) Polypropylene resin (Prime Polymer product "Prime Polypro J1") is used as a binder resin. The composition (molded body material) was prepared by compounding and mixing with polypropylene. The blending amount of the polypropylene resin depends on the content of the matrix resin (polypropylene) and the functional sustained release liquid ( The content of chlorpyrifos and the content of porous body (porous coordination polymer) are shown in the above table. The amount was set to be as shown in 5. The compounding method was the same as that described in Example 1. The material was molded into a plate-like body of 50×50 mm and 1.2 mm thick, which was designated Comparative Example 5-3.
[0146] [Comparative Example 5-4] The functional sustained-release liquid was chlorpyrifos, which was used in Example 31, and the metal ion was iron ion. A porous structure composed of cation (oxidation number 3, ionic radius 55 pm) and trimesic acid as an organic ligand. Coordination polymer (Fe-BTC, specific surface area by BET method: 1,754 m 2 / g, average pore size: 2.4~2.9nm ) as the matrix resin, and polypropylene resin (Prime Polymer's "Prime The composition (molded body material) was prepared by compounding and mixing with "Polypropylene J105G". The amount of polypropylene resin blended depends on the content of the matrix resin (polypropylene), the functionality, and the The content of the release liquid (chlorpyrifos) and the content of the porous body (porous coordination polymer) are The amounts were as shown in Table 5 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 5-4.
[0147] [Comparative Example 5-5] The functional sustained-release liquid was chlorpyrifos, which was used in Example 31, and chromium was used as the metal ion. A porous structure composed of terephthalic acid as an organic ligand. Polymeric coordination polymer ("MIL-101(Cr)"), surface area by BET method: 2,200 m 2 / g, average pore diameter: 2.0~ 2.7 nm) as the matrix resin, and polypropylene resin (Prime Polymer product "Prime Polymer" Compound and mix with "Lime Polypro J105G" to prepare a composition (molded body material) The amount of polypropylene resin used was determined by the matrix resin (polypropylene) content, Content of functional sustained-release liquid (chlorpyrifos) and porous body (porous coordination polymer) The amounts were set so that they were as shown in Table 5 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 5-5.
[0148] [Comparative Example 5-6] The functional sustained-release liquid was chlorpyrifos, which was used in Example 31, and the metal ion was nickel. Ion (oxidation number 1, ionic radius 68 pm), 2,5-dihydroxyterephthalic acid as organic ligand A porous coordination polymer composed of MOF-74-Ni (BET surface area: 1,360 m 2 / g, Average pore size: 1.0 nm) and polypropylene resin (Prime Polymer) as the matrix resin. - Compound and mix with the product "Prime Polypro J105G" to produce a composition (molded body) The amount of polypropylene resin blended was 1:1. ) content, functional sustained release liquid (chlorpyrifos) content and porous body (porous coordination polymer) The amounts of the components (a) and (b) were adjusted so that the contents of the components (a) and (b) were as shown in Table 5 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated as Comparative Example 5-6.
[0149] [Comparative Example 5-7] The functional sustained-release liquid was chlorpyrifos, which was used in Example 31, and the metal ion was zirconium. It is composed of ammonium ion (oxidation number 4, ionic radius 72 pm) and terephthalic acid as an organic ligand. A porous coordination polymer (Uio-66) with a BET surface area of 1,000 m 2 / g, average pore size: 0.9n m) is used as the matrix resin, and polypropylene resin (Prime Polymer's "Prime The composition (molded body material) was prepared by compounding and mixing with "Mupolypro J105G" The amount of polypropylene resin blended depends on the content of the matrix resin (polypropylene) and the functionality. The content of the sustained release liquid (chlorpyrphos) and the content of the porous body (porous coordination polymer) are The amounts were as shown in Table 5 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated as Comparative Example 5-7.
[0150] [Comparative Example 5-8] The functional sustained-release liquid was chlorpyrifos, which was used in Example 31, and the ion was copper ion (acid). The porous high-coordination structure is composed of trimesic acid as an organic ligand. Molecule ("Cu-BTC", BET surface area: 1,500 m 2 / g, average pore size: 0.9 nm) Polypropylene resin (Prime Polymer product "Prime Polypro J105") is used as the base resin. The composition (molded body material) was prepared by compounding and mixing with polypropylene. The amount of polypropylene resin blended is determined by the content of matrix resin (polypropylene), functional sustained release liquid ( The content of lorpyrifos) and the content of porous body (porous coordination polymer) are shown in Table 5. The amount was set to be as shown in FIG. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 5-8.
[0151] [Comparative Example 5-9] The functional sustained-release liquid was chlorpyrifos, which was used in Example 31, and the metal ion was zinc ion. It is composed of 2-methylimidazole as an organic ligand and 2-methylimidazole as an ionic ligand. A porous coordination polymer (ZIF-8) with a BET surface area of 1,400 m 2 / g, average pore diameter: 0.3~ 1.1 nm) as the matrix resin, and polypropylene resin (Prime Polymer product "Prime Polymer" Compound and mix with "Lime Polypro J105G" to prepare a composition (molded body material) The amount of polypropylene resin used was determined by the matrix resin (polypropylene) content, Content of functional sustained-release liquid (chlorpyrifos) and porous body (porous coordination polymer) The amounts were set so that they were as shown in Table 5 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 5-9.
[0152] [Comparative Example 6-1] Dimethyl sulfoxide, which was used in Example 33 as a functional sustained release liquid, was used as a matrix resin. Polypropylene resin (Prime Polymer product "Prime Polypro J105G") is used as the component. The mixture was pounded and mixed to produce a composition (molded body material). The amount of the matrix resin (polypropylene resin) and the functional sustained release liquid are The amounts were as shown in Table 6 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 6-1.
[0153] [Comparative Example 6-2] The functional sustained-release liquid was dimethyl sulfoxide, which was used in Example 33, and the metal ion was diphenyl ether. The compound is composed of an iron ion (oxidation number 4, ionic radius 72 pm) and terephthalic acid as an organic ligand. The porous coordination polymer (Uio-66, surface area measured by BET method: 1,000 m 2 / g, average pore size : 0.9 nm) as the matrix resin, and polypropylene resin (Prime Polymer product " The composition (molded body material) is made by compounding and mixing with "Prime Polypro J105G" The amount of polypropylene resin blended was determined based on the content of the matrix resin (polypropylene). , content of functional sustained release liquid (dimethyl sulfoxide) and porous body (porous coordination polymer) The contents of each of the above were set to be as shown in Table 6. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having dimensions of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 6-2.
[0154] [Comparative Example 6-3] The functional sustained-release liquid was dimethyl sulfoxide, which was used in Example 33, and the metal ion was copper. Polyamines consisting of an ion (oxidation number 2, ionic radius 73 pm) and trimesic acid as an organic ligand. Porous coordination polymer (Cu-BTC, BET surface area: 1,500 m 2 / g, average pore diameter: 0.9nm) The matrix resin is polypropylene resin (Prime Polymer product "PrimePo The composition (molded body material) was prepared by compounding and mixing with the "Repro J105G" resin. The amount of polypropylene resin blended depends on the content of the matrix resin (polypropylene) and the functional sustained release The content of the reactive liquid (dimethyl sulfoxide) and the content of the porous body (porous coordination polymer) The amounts were as shown in Table 6 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having dimensions of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 6-3.
[0155] [Comparative Example 6-4] The functional sustained-release liquid was dimethyl sulfoxide, which was used in Example 33, and the metal ion was nitrous oxide. It is composed of lead ion (oxidation number 2, ionic radius 74 pm) and 2-methylimidazole as an organic ligand. The porous coordination polymer (ZIF-8) is a porous material with a BET surface area of 1,400 m 2 / g, average pore size : 0.3 to 1.1 nm) and polypropylene resin (Prime Polymer product) as the matrix resin. "Prime Polypro J105G") is compounded and mixed to produce the composition (molded body material). The amount of polypropylene resin blended was determined based on the content of the matrix resin (polypropylene). The amount of functional sustained release liquid (dimethyl sulfoxide) and the amount of porous material (porous coordination polymer) The amounts of the components (a) and (b) were adjusted so that the contents of the components (a) and (b) were as shown in Table 6 above. The compounding method was the same as that described in Example 1. The mixture was molded into a plate-like product having a size of 50×50 mm and a thickness of 1.2 mm, which was designated Comparative Example 6-4.
[0156] (Evaluation of liquid sustained release properties) The samples of the examples and comparative examples were evaluated for their sustained release properties by the following method. First, each sample (molded body) was immersed in 50 mL of tetrahydrofuran in a 20°C environment, and the surface The functional sustained-release liquid precipitated on the surface was washed. The concentration of the functional sustained-release liquid component in the washing liquid was measured, and the surface amount per unit area of the sample ( Unit: μg / cm 2 This was measured 10 times, once every 24 hours.
[0157] The evaluation results are shown in Tables 1 to 6. The exponential function formulas shown in Tables 1 to 6 are obtained by repeating the process shown in FIGS. 1 is an approximation of the graph of the surface area of the functional sustained release composite molded body versus the number of repeated washings. Formula: y=Ae -Bx y is the surface amount of the functional sustained release liquid, x is the number of repeated washings, and A is the functional sustained release liquid The initial value of the surface amount of the functional sustained-release liquid, the power index B is the magnitude of change in the surface amount of the functional sustained-release liquid after repeated cleaning. The larger the exponent, the greater the change in surface area due to repeated washing. Therefore, the release rate of the functional sustained-release liquid is unstable. In order to stabilize the liquid, it is desirable for the exponent to be small. It was used as an indicator of release.
[0158] More stable sustained release than when functional sustained-release liquid was kneaded into the base material alone (Comparative Examples 1 to 6) In order to find a functional sustained-release material having the above properties, the base was determined for each functional sustained-release liquid component for each example. The exponent value of the approximation equation when the functional sustained-release liquid is kneaded into the single material (Comparative Examples 1 to 6) The ratio was calculated. The upper limit is set at 0.90. If the power index ratio is too low, sustained release cannot be achieved. Therefore, the lower limit was set to 0.1. Therefore, the acceptable range of the exponent ratio is from 0.10 to 0.90. Ta.
[0159] Based on the results obtained, the physical properties of the functional sustained-release liquid and the porous body were thoroughly examined. The following relationships could be found for the power exponent ratios: First, the relationship between the exponent ratio and the metal ion radius of the porous body in each example is shown in Figs. As is clear from Figures 65 to 70, in all the Examples, the results were statistically significant for each functional sustained-release liquid. The exponential ratio and the metal ion radius of the porous body have a strong correlation with a linear approximation coefficient of determination of 0.90 or more. Therefore, the power exponent can be expressed by the following approximation: Approximation of the power exponent ratio: Y = C × R + D Equation 4 In the formula 4, R is the radius of the metal ion, C is the slope, and D is the intercept. Furthermore, for the slope C and intercept D of the linear approximation equations shown in Figures 65 to 70, The relationship between the acid dissociation constant and the acid dissociation constant is shown in Figures 71 and 72, respectively. These relationships are expressed by the linear approximation formula The coefficient of determination was over 0.90, indicating a high correlation. C=0.0013α-0.079...Equation 5 D=-0.1082α+1.436...Equation 6 Here, in formulas 5 and 6, α represents the acid dissociation constant of the functional sustained-release liquid. Therefore, since the acceptable range of the exponent ratio is 0.10 to 0.90, the exponent ratio is The acid dissociation constant α of the property liquid and the metal ion radius R can be arranged as follows. 0.10 < Y = C×R + D < 0.90 ··· Equation 7 0.10 < (0.0013α - 0.0079)R + (-0.1082α + 1.436) < 0.90 ··· Equation 8 JPEG2025066142000015.jpg22129
[0160] From the above Equation 1, the range of the acid dissociation constant and the metal ion radius for obtaining excellent sustained release properties is shown ( Figure 73). The range for obtaining excellent sustained release properties is the shaded part in Figure 73. All the plots shown outside the shaded part have a power exponent ratio exceeding 0.90 or less than 0.10, indicating that they are inappropriate combinations. Therefore, in order to maintain an excellent sustained release effect over a long period, it is required to use the acid dissociation constant of the functional sustained release liquid satisfying Equation 1 and the metal ion radius of the porous body.
Industrial Applicability
[0161] The functional sustained release composition of this embodiment can be used, for example, for molded articles imparted with functional components such as small animal control functions, sliding functions, antibacterial functions, fungicidal functions, self - repair functions, catalytic functions, and medical functions. Specifically, the functional sustained release composite molded body of this embodiment can be used in industrial fields such as automobiles and electrical products, amenity fields such as sanitary services, and the pharmaceutical field.
Claims
1. A porous body having a functional sustained-release liquid and metal ions is provided, and the acid dissociation constant α of the functional sustained-release liquid is wherein the radius R of the metal ion satisfies the range of the following formula 1: A composition and a molded article thereof.
2. The metal ion is at least one of an alkali metal, an alkaline earth metal, and a transition metal.
2. The functional sustained-release composition and its molded product according to claim 1,
3. The radius R of the metal ion is 40×10 -12 m to 150 x 10 -12 m 3. The functional sustained-release composition and its molded article according to claim 1 or 2.
4. The acid dissociation constant α of the functional sustained-release liquid is within the range of −10 to 40. Item 4. The functional sustained-release composition and its molded body according to Items 1 to 3.
5. The porous material is preferably a porous coordination polymer consisting of metal ions and organic ligands. The functional sustained-release composition and its molded product according to claims 1 to 4.
Citation Information
Patent Citations
Small animal-controlling resin composition and small animal-controlling member prepared by molding the same
JP2000212005A
Canister structure for vehicle
JP2001073886A
Termite-proof sheet
JP2008206492A
Small animal controlling resin composition
JP2012006868A
Functional sustained-release composition and molding
JP2019218310A